Composition for tissue regeneration and preparation method thereof
By combining heterogeneous decellularized extracellular matrix and natural polymers, using nano-patterned surface morphology, a composition with enhanced antibacterial properties was developed, which solved the infection problems in tissue regeneration and wound healing, and achieved efficient tissue repair and antibacterial effects.
Patent Information
- Application Number
- CN202480002631.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-19
- Filing Date
- 2024-04-18
- Publication Date
- 2025-01-17
AI Technical Summary
The prior art is difficult to effectively solve the infection problem during tissue regeneration and wound healing, and the antibacterial properties of existing materials are insufficient, affecting the healing efficiency.
A composition is developed that comprises heterogeneous decellularized extracellular matrix (dECM) components and natural polymer components to enhance the antibacterial properties of the composition through decellularization process and chemical modification, combined with nanopatterned surface morphology.
The composition significantly accelerates the repair of damaged or defective bones or injured skin, has enhanced biocompatibility, antibacterial properties and versatility, reduces the risk of postoperative infection and promotes tissue healing.
Smart Images

Figure CN119325395A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 497,006, the entire contents of which are incorporated herein by reference. Technical Field
[0003] The present disclosure relates to compositions for tissue regeneration and wound healing and methods for preparing the same. In particular, the present disclosure relates to compositions for tissue regeneration, comprising (1) a heterogeneous decellularized extracellular matrix (dECM) component, and (2) a polymer component. The composition has enhanced antibacterial properties. Background Art
[0004] dECM tissue regeneration utilizes decellularized extracellular matrix (dECM) scaffolds to promote tissue repair and regeneration. By removing cellular components while retaining the native extracellular matrix structure, dECM scaffolds or platforms serve as templates for cell adhesion, proliferation, and differentiation. These scaffolds have potential applications in a variety of fields, including tissue engineering and wound healing, offering advantages such as biocompatibility, bioactivity, and versatility.
[0005] There is a need for a composition for tissue regeneration and wound healing and a method for preparing the same, which promotes tissue healing while reducing problems associated with postoperative infection. Summary of the invention
[0006] Tissue engineering and regeneration aim to prepare substitutes, structures or platforms for repairing damaged tissues by using biomaterial scaffolds that mimic the natural extracellular matrix (ECM) environment. Decellularized extracellular matrix (dECM) scaffolds advantageously provide an effective biomimetic platform for regenerative medicine.
[0007] According to a first aspect of the present disclosure, a composition for tissue regeneration in a subject is provided. The composition comprises: a xenogeneic decellularized extracellular matrix (dECM) component containing a biomaterial and a polymer component, wherein the composition is prepared by a method comprising:
[0008] (i) isolating tissue from a donor animal to obtain the biological material;
[0009] (ii) decellularizing the biomaterial to obtain the decellularized extracellular matrix component; and
[0010] (iii) combining the decellularized extracellular matrix component with the polymer component to produce the composition with enhanced antimicrobial properties.
[0011] For example, the tissue is selected from one or more of the fetal membranes, or fetal or neonatal bones of the donor animal. In another example, the donor animal is a goat fetus or goat neonate. In one example, the donor animal is a goat fetus or goat neonate with a gestational age of about 12 weeks to about 18 weeks.
[0012] The compositions of the present disclosure advantageously combine the biomimetic properties of the decellularized extracellular matrix component with a polymer component that enhances its antimicrobial properties, thereby accelerating the repair of damaged or defective bone or injured skin when used. Thus, the compositions exhibit enhanced biocompatibility, customizability, and versatility.
[0013] In an exemplary embodiment, the composition includes a xenogeneic decellularized extracellular matrix (dECM) component containing a biomaterial. The biomaterial is obtained from the tissue of a donor animal. In one example, the tissue is selected from one or more of the fetal membrane tissue and / or fetal bone tissue of the donor animal. The fetal membrane tissue includes, for example, one or more of the amnion and / or the chorion. The fetal bone tissue includes, for example, one or more of the cortical bone and / or the cancellous bone. The use of xenogeneic dECM also has the advantage of increasing availability and is more widely accepted in view of religious concerns, etc. In an exemplary embodiment, the decellularized extracellular matrix component is in the form of a powder, a solution, a hydrogel, a scaffold, a membrane, a film, a coating, or a combination thereof. The surface morphology of the decellularized extracellular matrix component is porous, smooth, nano-patterned, or a combination thereof.
[0014] The decellularized extracellular matrix component is combined with a polymer component. In one example, the polymer component is a membrane, a scaffold, a hydrogel, or a combination thereof. In another example, the surface morphology of the polymer component is porous, smooth, nano-patterned, or a combination thereof. The nano-pattern morphology of the surface of the polymer component and / or the decellularized extracellular matrix component advantageously provides enhanced antibacterial properties for the composition. In another embodiment, the decellularized extracellular matrix component and / or the polymer component comprises a tightly packed array of nanocones.
[0015] In an exemplary embodiment, the polymer component is derived from one or more natural polymers. The natural polymer includes but is not limited to: silk fibroin, chitosan or a combination thereof. In an exemplary embodiment, the silk fibroin is a stretchable film or a hard film.
[0016] In another exemplary embodiment, the polymer component is pure chitosan or functionalized chitosan. For example, the polymer component is functionalized chitosan produced by mixing chitosan with N-(β-maleimidopropoxy) succinimide ester at room temperature for about 6 hours.
[0017] In a preferred embodiment, the composition is a hydrogel, a scaffold, a membrane or a coating.
[0018] In an exemplary embodiment, the composition is applied to the skin or bone tissue of a mammalian subject in need of tissue repair. For example, the skin in need of repair has been injured, such as a chronic wound or an infected skin wound, or a burn, or a combination thereof. In addition, the composition promotes and / or accelerates the repair of injured or defective bone tissue or injured skin, and has effective antimicrobial properties.
[0019] According to a second aspect of the present disclosure, there is provided a method for preparing a decellularized extracellular membrane (dECM) composition for tissue regeneration in a subject, the composition comprising a decellularized extracellular matrix component and a polymer component, the method comprising the following steps:
[0020] (i) obtaining target tissue from a donor animal;
[0021] (ii) decellularizing the target tissue and removing genetic material from the target tissue to obtain the decellularized extracellular matrix component; and
[0022] (iii) combining the decellularized extracellular matrix component with the polymer component to prepare a composition with enhanced antimicrobial properties.
[0023] In a preferred embodiment, decellularizing the target tissue comprises: treating the target tissue with a chemical reagent, wherein the chemical reagent comprises a detergent, an enzyme, a chelating agent, or a combination thereof. In one example, the detergent is Triton-x; the enzyme is DNase; and the chelating agent is ethylenediaminetetraacetic acid (EDTA). The decellularized extracellular matrix components are produced in a manner that preferentially maintains structure and biological activity, and the method includes the use of detergents, enzymes, chelating agents, mechanical methods, and combinations thereof. Complete decellularization is further achieved by removing genetic material with nucleases to prevent host immune responses. In an exemplary embodiment, the decellularized extracellular matrix components are present in a non-fragmented, fragmented, ground, or dissolved form. In another exemplary embodiment, the decellularized extracellular membrane (dECM) composition has a complex 3D structure, such as a 3D scaffold, spheroid, fiber, or sheet.
[0024] In one embodiment, decellularizing the target tissue comprises the following steps:
[0025] (i) washing the tissue in a hypotonic buffer optionally supplemented with antibiotics, chelators, and a protease inhibitor cocktail;
[0026] (ii) washing the tissue in an isotonic buffer, wherein the isotonic buffer optionally contains a detergent, a chelating agent, a protease inhibitor cocktail, and an antibiotic;
[0027] (iii) washing the tissue with an isotonic buffer;
[0028] (iv) washing the tissue in a hypotonic buffer; and
[0029] (v) washing the tissue with an isotonic buffer and removing genetic material from the target tissue to obtain a decellularized extracellular matrix component.
[0030] In one embodiment, steps (i) to (v) comprise shaking the target tissue at about 100 rpm to about 500 rpm. In addition, decellularizing the target tissue comprises the optional step of physically disrupting the target tissue by freeze-thawing, grinding, homogenization, osmotic shock, or a combination thereof.
[0031] In another embodiment, step (ii) comprises a step of reducing the size of the target tissue, for example by grinding. Mechanical disruption of the tissue by freeze-thawing, grinding or homogenization can disrupt cell membranes and release cellular components.
[0032] In another embodiment, the polymer component is derived from one or more natural polymers. In an example, the polymer component is silk-fibroin, chitosan or a combination thereof. When the polymer component is silk-fibroin, it exists in a stretchable film or a rigid film form.
[0033] In another exemplary embodiment, the polymer component is pure chitosan or functionalized chitosan. In one example, the functionalized chitosan is produced by mixing chitosan with N-(β-maleimidopropoxy) succinimide ester at room temperature for about 6 hours.
[0034] In an exemplary embodiment, the polymer component is a membrane, a scaffold, a hydrogel or a combination thereof. Further, the surface morphology of the polymer component and / or the decellularized extracellular matrix component is porous, smooth, nano-patterned or a combination thereof. Preferably, the nano-patterned surface morphology of the decellularized extracellular matrix component and / or the polymer component provides enhanced antibacterial properties for the decellularized extracellular membrane (dECM) composition.
[0035] In another embodiment, the decellularized extracellular matrix component is in the form of a powder, a hydrogel, a scaffold, a membrane, a film, a coating or a combination thereof.
[0036] In a preferred embodiment, the decellularized extracellular membrane (dECM) composition is a scaffold, a membrane or a coating.
[0037] In an exemplary embodiment, the donor animal is a goat fetus or a goat neonate; the target tissue is selected from one or more of fetal membranes, or fetal or neonatal bones from the donor animal. Preferably, the donor animal is a goat fetus or a goat neonate with a gestational age of about 12 weeks to about 18 weeks.
[0038] In one embodiment, the target tissue is selected from one or more of fetal membrane tissue and / or fetal or neonatal bone tissue from the donor animal. In one example, the fetal membrane tissue includes one or more of amnion and / or chorion. In another example, the fetal or neonatal bone tissue includes one or more of cortical bone and / or cancellous bone.
[0039] In a preferred embodiment, the decellularized extracellular membrane (dECM) composition is applied to the skin or bone tissue of a subject in need of tissue repair, including but not limited to, for example, repair of susceptible tissue. According to another aspect of the present disclosure, a method for repairing the skin or bone tissue of a subject is provided. The method comprises: applying the aforementioned decellularized extracellular membrane (dECM) composition to the skin or bone tissue of a subject in need of tissue repair.
[0040] The claimed compositions and methods of preparation thereof exhibit enhanced biocompatibility, modularity, and versatility for tissue engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Embodiments of the present disclosure will be described below by way of examples with reference to the accompanying drawings.
[0042] Figures 1A to 1C An image of goat fetal membrane (ACM) is shown. Prior to the washing step, the epithelial layer and blood residues were removed by a cell scraper.
[0043] Figures 2A to 2C An image of freeze-dried dECM of goat ACM is shown. Figure 2A Shown is freeze-dried dECM before grinding. Figure 2B Shown is freeze-dried dECM after grinding. Figure 2C Pepsin-digested decellularized extracellular matrix components are shown. The prepared solution was freeze-dried again to obtain dECM powder denoted as "dACM".
[0044] Figure 3A and 3B Figure 2 shows the gelation behavior of composites prepared from βMPS-modified chitosan hydrogels denoted as “BMPS” and dACM particles named “BMPS-dACM”. The hydrogel solution is liquid at 25°C and is injectable ( Figure 3A), while after incubation at -20 °C for 24 h, it can be cross-linked and become a stable hydrogel at 37 °C ( Figure 3B ).
[0045] Figure 4 Scanning electron microscope (SEM) image of coated polystyrene nanospheres on plasticized silk matrix.
[0046] Figure 5A Photo of a nanopatterned stretchable mesh. Figure 5B and 5C is a SEM image showing nanocone arrays fabricated from stretchable silk on a silk substrate.
[0047] Figure 6 Photograph of a composite wound dressing scaffold (“ChitoSilk BioPatch”) prepared by combining a stretchable nanopatterned silk mesh and BMPS-dACM hydrogel.
[0048] Figure 7 The figure shows the comparison of DNA content between non-decellularized tissue as control and decellularized extracellular matrix component prepared by the method of Example 1.
[0049] Fig. 8A and 8B H&E staining images of goat fetal membranes (ACM). Fig. 8A is a non-decellularized image, Figure 8B This is an image after decellularization using the method of Example 1. Cell nuclei (black dots, indicated by arrows) are more obvious in the control ACM, but cannot be distinguished in the decellularized extracellular matrix component.
[0050] Fig.9A and 9B Trichrome staining of ACM is shown. Fig.9A Non-decellularized staining is shown as a control. Fig. 9B Shown is the staining of the decellularized extracellular matrix component obtained using the decellularization method of Example 1. Cell nuclei (black dots, indicated by arrows) are visible in the control ACM but not in the decellularized extracellular matrix component.
[0051] Fig.10 3 is a graph showing a comparison of the collagen content of the ACM samples before (control) and after decellularization using the decellularization method of Example 1.
[0052] Fig.11A and 11B To show the extreme dry conditions (dehydration treatment) ( Fig.11A ) and normal atmospheric pressure conditions ( Fig. 11B ) with different ratios of CaCl2 Comparison of the compressive elastic modulus of the stretchable silk matrix prepared with formic acid.
[0053] Fig.12 A comparison of the compressive elastic modulus of a stretchable silk matrix prepared with a 3% CaCl2 to formic acid ratio maintained under extreme dry conditions (dry) and normal atmospheric pressure (non-dry) and wet conditions is shown. The compressive elastic modulus of a substrate with nanocones on its surface under wet conditions is also shown.
[0054] Fig.13 Shown are photographs of agar plates on which Staphylococcus aureus bacterial cells were recultured as follows: no treatment (control), treatment with pure chitosan hydrogel ("CS"), treatment with βMPS-chitosan hydrogel ("BMPS"), and treatment with βMPS-chitosan incorporated with dACM particles ("BMPS-dACM") for 1, 3, 6, and 24 hours.
[0055] Fig.14 The figure shows the comparison of the antibacterial rates of BMPS and BMPS-dACM relative to CS hydrogel against Staphylococcus aureus at different time points.
[0056] Fig.15 Shown are photographs of agar plates on which P. aeruginosa bacterial cells were re-cultured as follows: no treatment (control), treatment with CS, treatment with BMPS, and treatment with BMPS-dACM for 1, 3, 6, and 24 hours.
[0057] Fig.16 Shown are photographs of agar plates on which Staphylococcus aureus bacterial cells were re-cultured as follows: no treatment (control), treatment with silk, and treatment with nanopatterned silk for 1, 3, 6, and 24 hours.
[0058] Fig.17 Shown are photographs of agar plates on which Pseudomonas aeruginosa bacterial cells were re-cultured as follows: no treatment (control), treatment with silk, and treatment with nanopatterned silk for 1, 3, 6, and 24 hours.
[0059] Figures 18A to 18D To cultivate silk ( Fig.18A and 18B ) and nanopatterned wires ( Fig.18C and 18D Scanning electron microscope (SEM) images of Staphylococcus aureus on silk substrates with a 6-hour incubation time. These images confirm the antibacterial effect of silk nanocones against Staphylococcus aureus compared to silk substrates without nanopatterns.
[0060] Figures 19A to 19D To cultivate silk ( Fig.19A and 19B ) and nanopatterned wires ( Fig.19C and 19D Scanning electron microscope (SEM) images of Staphylococcus aureus on silk substrates with a culture time of 24 hours. These images confirm the antibacterial effect of silk nanocones against Staphylococcus aureus compared to silk substrates without nanopatterns.
[0061] Figures 20A to 20D To cultivate silk ( Fig. 20A and 20B ) and nanopatterned wires ( Fig. 20C and 20D Scanning electron microscope (SEM) images of Pseudomonas aeruginosa on silk substrates with a culture time of 3 hours. These images confirm the antibacterial effect of silk nanocones against Pseudomonas aeruginosa compared to silk substrates without nanopatterns.
[0062] Figures 21A to 21D To cultivate silk ( Fig.21A and 21B ) and nanopatterned wires ( Fig. 21C and 21D Scanning electron microscope (SEM) images of Pseudomonas aeruginosa on silk substrates with a culture time of 24 hours. These images confirm the antibacterial effect of silk nanocones against Pseudomonas aeruginosa compared to silk substrates without nanopatterns.
[0063] Fig.22A A and B show the dynamic changes in diabetic wound area after full-thickness skin defect surgery. Fig.22A In, macroscopic observations of diabetic wounds in each group on days 0, 1, 4, 7, 10, and 14 are shown, as well as quantitative evaluations of wound closure rates on days 10 and 14 after treatment with different wound dressings. Fig. 22B Figure 2 shows the H&E staining results of the wound bed in each group on days 7 and 14. *p<0.05, **p<0.01 vs. NC group. ^p<0.05, ^^p<0.01 vs. CS group. #p<0.05, ##p<0.01 vs. BMPS group. &p<0.05, &&p<0.01 vs. BMPS-dACM group. n=6 / group / time point.
[0064] Fig.23A C to C show collagen deposition in the diabetic wound area after full-thickness skin defect surgery. Fig.23A In Figure , the Sirius red staining results of the wound bed in each group on days 7 and 14 are shown. Fig. 23BIn the figure, the quantitative evaluation of collagen I positive area, collagen III positive area and collagen I / collagen III ratio based on Sirius red staining on day 7 is shown. And the quantitative evaluation of collagen I positive area, collagen III positive area and collagen I / collagen III ratio based on Sirius red staining on day 14 is shown. *p<0.05, **p<0.01vs.NC group. ^p<0.05, ^^p<0.01vs.CS group. #p<0.05, ##p<0.01vs.BMPS group. &p<0.05, &&p<0.01vs.BMPS-dACM group. n=6 / group / time point.
[0065] Figures 24A to 24D The detection of macrophage subsets in the diabetic wound area at day 7 after full-thickness skin defect surgery is shown. Fig.24A In the figure, double label IF staining of F4 / 80 and iNOS in the wound bed in each group on day 7 is shown. Fig. 24B In Figure , double-label IF staining of F4 / 80 and CD206 of the wound bed in each group on day 7 is shown. Fig.24C In Figure 2, a semi-quantitative analysis of F4 / 80 and iNOS double positive cells is shown. Fig.24D In the figure, semi-quantitative analysis of F4 / 80 and CD206 double positive cells is shown. *p<0.05, **p<0.01 vs. NC group. ^p<0.05, ^^p<0.01 vs. CS group. #p<0.05, ##p<0.01 vs. BMPS group. &p<0.05, &&p<0.01 vs. BMPS-dACM group. n=6 / group / time point.
[0066] Fig.25A and 25B Shown is the neovascularization in the diabetic wound area 14 days after full-thickness skin defect surgery. Fig.25A In Figure 2, double-label IF staining of CD31 and α-SMA in the wound bed of each group on day 14 is shown. Fig.25B In the figure, semi-quantitative analysis of blood vessels is shown, which are marked by CD31 and α-SMA double positivity. *p<0.05, **p<0.01 vs. NC group. ^p<0.05, ^^p<0.01 vs. CS group. #p<0.05, ##p<0.01 vs. BMPS group. &p<0.05, &&p<0.01 vs. BMPS-dACM group. n=6 / group / time point.
[0067] Figures 26A to 26D shows that after removing muscle, fat and skin ( Fig.26A ) after being cut into small pieces using surgical tools ( Fig.26B), and then ground into small particles for decellularization ( Fig.26C ). Fig.26D Images of decellularized extracellular matrix components of fetal goat bone after freeze drying.
[0068] Fig. 27 FIG. 5 is a graph showing a comparison of DNA content of goat fetal bones including fetal bone dECM (dECM) and demineralized fetal bone dECM (demineralized dECM) that were not decellularized as a control or decellularized using method 2. FIG.
[0069] Figures 28A to 28C Shown are H&E stained images of fetal goat bone samples. Fig.28A Non-decellularized controls are shown, Fig.28B Decellularized ECM is shown. Fig.28C It shows the decellularized and demineralized bone ECM prepared by the decellularization and / or demineralization method of Example 2. The cell nuclei (black dots, indicated by arrows) are more obvious in the control tissue, but cannot be distinguished in the dECM and demineralized dECM.
[0070] Figures 29A to 29C Shown is a trichrome stain of fetal goat periosteum. Fig.29A Non-decellularized controls are shown, Fig.29B Decellularized ECM is shown. Fig.29C Shown is a decellularized and demineralized ECM prepared using the decellularization and / or demineralization method of Example 2. Cell nuclei (black dots, indicated by arrows) are visible in the control but not in the dECM, although collagen fibers are well preserved during decellularization and demineralization.
[0071] Fig.30 Shown are SEM images of unreinforced fetal goat bone dECM-silk membranes prepared at different silk to demineralized bone dECM digestion product ratios.
[0072] Fig.31A and 31B Shown is an SEM image of nanopatterned unreinforced dECM-silk (1:1) demonstrating the fibril morphology of the membrane with hexagonally close-packed nanocone arrays on the surface.
[0073] Figures 32A to 32D demonstrated a 2% dECM-silk hybrid composite ( Fig.32A and 32B ) and its nanopatterned counterpart ( Fig.32C and 32D Yellow arrows indicate the dispersion of fetal bone dECM particles with a size of ≤200 μm in the matrix.
[0074] Fig.33 Shown are photographs of agar plates on which Staphylococcus aureus bacterial cells were cultured after treatment with negative control and nanopatterned 2% dECM-silk hybrid composites for 3 hours.
[0075] Fig.34 A photo of an agar plate is shown. 2 Plasma-etched unreinforced dECM-silk (1:1), nanopatterned unreinforced dECM-silk (1:1), O 2 Plasma-etched 2% dECM-silk hybrid composites, nanopatterned 2% dECM-silk hybrid composites and ciprofloxacin at a concentration of (20 mg / mL) as a positive control were treated for 1, 3, 6 and 24 hours, and then Staphylococcus aureus bacterial cells were cultured.
[0076] Figures 35A to 35D For O 2 Plasma-etched non-reinforced dECM-silk (1:1) ( Fig.35A and 35B ) and in nanopatterned non-reinforced dECM-silk (1:1) ( Fig.35C and 35D ) for 3 hours, confirming the antibacterial properties of both samples, as the bacterial cell wall was damaged when cultured on these surfaces. However, the synergistic effect of the nanocones interacting with the cell wall and the dECM AMPs from fetal demineralized bone in the nanopatterned non-reinforced dECM-silk (1:1) matrix resulted in a significant reduction in attached bacteria on the surface.
[0077] Figures 36A to 36D For O 2 Plasma-etched 2% dECM-silk hybrid composite ( Fig.36A and 36B ) and in nanopatterned 2% dECM-silk hybrid composites ( Fig.36C and 36D ) for 3 hours, confirming the antibacterial properties of both samples due to damage to the bacterial cell wall when cultured on these surfaces. However, the synergistic effect of the cell wall-interacting nanocones used in the substrate of the nanopatterned 2% dECM-silk hybrid composite and the dECM AMPs from fetal bone (mineralized and demineralized) resulted in significantly fewer bacteria attached to the surface and more significant bacterial membrane damage.
[0078] Figures 37A to 37D For O 2Plasma-etched non-reinforced dECM-silk (1:1) ( Fig.37A and 37B ) and in nanopatterned non-reinforced dECM-silk (1:1) ( Fig.37C and 37D ) for 24 hours, confirming the antibacterial properties of both samples, as the bacterial cell wall was damaged when cultured on these surfaces. However, the synergistic effect of the nanocones interacting with the cell wall and the dECM AMPs from fetal demineralized bone in the nanopatterned non-reinforced dECM-silk (1:1) matrix resulted in a significant reduction in attached bacteria on the surface.
[0079] Figures 38A to 38D For O 2 Plasma-etched 2% dECM-silk hybrid composite ( Fig.38A and 38B ) and cultured on nanopatterned 2% dECM-silk hybrid composites ( Fig.38C and 38D ) with an incubation time of 24 hours, which confirms the antibacterial properties of both samples due to the damage to the bacterial cell wall when incubated on these surfaces. However, the synergistic effect of both (mineralized and demineralized) nanocones and fetal bone dECM AMPs used in the matrix of the nanopatterned 2% dECM-silk hybrid composite resulted in a significant reduction in bacteria attached to the surface and more severe bacterial membrane damage. Almost no bacteria survived on the surface, only visible bacterial fragments. DETAILED DESCRIPTION
[0080] Definition of terms
[0081] As used herein, the term "subject" refers to an animal in need or desire of delivering the benefit provided by a therapeutic compound. The term "animal" as used herein may be, for example, a human, pig, horse, goat, cat, mouse, rat, dog, ape, fish, chimpanzee, orangutan, guinea pig, hamster, cow, sheep, bird, chicken, and any other vertebrate or invertebrate. These benefits may include, but are not limited to, treating a health condition, disease, or condition; preventing a health condition, disease, or disorder; immune health; enhancing the function of an organ, tissue, or system in the body. The preferred subject in the context of this disclosure is a human. The subject may be of any age or developmental stage.
[0082] As used herein, the term "treat" refers to eradicating, alleviating, ameliorating or reversing the signs or symptoms of a health condition, disease or disorder to any extent, and includes but does not require complete cure of the condition, disease or disorder. Treatment can be a cure, amelioration or partial amelioration of the condition. "Treatment" can also include improving or enhancing a condition or feature, for example, bringing the function of a particular system in the body to an enhanced state of health or homeostasis.
[0083] As used herein, the term "cellular components" refers to the cell membrane, cytoplasm, dsDNA, and organelles (eg, nucleus, mitochondria, endoplasmic reticulum, Golgi apparatus, lysosome) constituting a cell.
[0084] As used herein, the term "decellularized ECM (dECM)" refers to the removal of cellular components and related debris from ECM during digestion, including, for example, DNA, RNA, and nuclei. The term "acellular" ECM or tissue, such as fetal membranes (amniotic membranes and / or chorionic membranes) and / or bones, refers to the "dECM" of related tissues, which can be used interchangeably. As used herein, the term "decellularization" refers to the removal of cellular components by using chemical means, that is, at least 75%, 80%, 85%, 90%, 95%, 96%, 97%, 98%, 99% or more. Decellularization can be measured by quantifying the DNA content of the extracellular matrix (ECM) per unit weight of stem cells.
[0085] As used herein, the terms "composition" and / or "decellularized extracellular membrane (dECM) composition" refer to any biomaterial, scaffold, construct, film, membrane, hydrogel, powder, particle, implant, drug delivery system, platform, composite, or any medical device composed of at least one type of dECM.
[0086] As used herein, the terms "scaffold," "bioscaffold," "implant," "bioimplant," "construct," "bioconstruct," "composite," "biocomposite," "medical device," and "biomedical device" are used interchangeably.
[0087] As used herein, "scaffold" refers to a temporary or permanent structure used as a support system to aid tissue growth and regeneration in damaged or diseased areas. On the other hand, a "bioscaffold" is a scaffold made of biocompatible materials that can support the growth of living tissue and eventually integrate with the body's natural tissues.
[0088] As used herein, the term "fetal membrane" refers to the combination of "amnion and chorion" or "amnio-chorionic membrane (ACM)", which are used interchangeably. "Fetal membrane" as used herein refers to the membranes that surround and protect the developing fetus during pregnancy. There are two main fetal membranes: the amnion and the chorion. The amnion is the innermost membrane that surrounds the developing fetus and is filled with amniotic fluid, which provides cushioning and protection for the developing fetus. The chorion is the outermost membrane that contacts the uterine wall and helps form the placenta, which provides nutrients and oxygen to the developing fetus.
[0089] As used herein, the term "amnion" refers to "amniotic membrane" which is used interchangeably. As used herein, "amnion" refers to the thin, tough, and transparent membrane that forms the innermost layer of the fetal membranes that surround and protect the developing embryo or fetus during pregnancy. It is filled with amniotic fluid, which has several important functions, such as cushioning the fetus, maintaining a constant temperature, and providing a medium for fetal movement and growth.
[0090] As used herein, the term "chorion" refers to the interchangeable term "chorionic membrane". As used herein, "chorion" refers to one of the two fetal membranes that surround and protect the developing embryo or fetus during pregnancy. It forms the outermost layer of the fetal membranes and is located near the uterus. The chorion plays a key role in the development of the placenta, an organ that provides oxygen and nutrients to the fetus and removes waste. The chorionic villi are finger-like projections that extend from the chorion to the lining of the uterus, allowing the exchange of nutrients, oxygen, and waste between the mother and the fetus.
[0091] As used herein, the terms "substrate," "film," and "membrane" are used interchangeably.
[0092] As used herein, the terms "nano pattern", "nano features" and "nanotopography" are used interchangeably. As used herein, "nano pattern" refers to a pattern on the surface of a material / structure having at least one dimension in the nanometer range (generally less than 100nm). Nano patterns can be produced by various methods, such as using nano-sized materials / particles, chemical patterning, self-assembly, lithography, nanoimprint lithography, colloidal lithography, soft lithography, 3D bioprinting, etc. These nanoscale patterns can have a uniform distribution on the surface of a material, with a wide range of shapes, including points, pits, columns, columns, lines, gratings or complex geometric shapes. As used herein, the term "nano features" generally refers to features or geometric structures having at least one nanoscale dimension (between 1nm and 1000nm), which may have different shapes (grooves, grids, pits, columns, cones, etc.). As used herein, the term "nanotopography" refers to an array of surface features of a material or substrate having a size of at least one submicron size or nanometer scale (1 to 1000nm). In the context of tissue engineering and regenerative medicine, nanotopography can be used to modulate cell fate and tissue growth.
[0093] As used herein, the terms "hydrogel" and "gel" are used interchangeably and refer to a 3D polymer structure that is insoluble in liquids (such as water) while being able to absorb large amounts of liquid to form a stable and generally soft and flexible structure.
[0094] Decellularized extracellular matrix (dECM) offers unique advantages that make it well suited for applications in tissue engineering and regenerative medicine. Some of these advantages include that dECM maintains the same biochemical composition and biomechanical properties as the donor tissue from which it is derived, advantageously providing high biocompatibility and bioactivity. dECM signaling mimics the natural microenvironment of the donor tissue, so that growth factors, cytokines, and cell adhesion peptides in dECM beneficially promote and achieve cell adhesion, proliferation, differentiation, and tissue remodeling.
[0095] dECM can be used as a biomimetic scaffold composition, biomaterial or biostructure in tissue engineering and regenerative medicine to support and promote the regeneration of functional tissues and organs. Compositions based on dECM advantageously promote cell migration, proliferation and tissue remodeling. It advantageously promotes angiogenesis, the formation of new blood vessels, and mobilizes endogenous stem cells to the site of injury, enhancing the regenerative capacity of damaged tissues.
[0096] Furthermore, by varying factors such as selecting tissue from different donors or sources, changing the decellularization method, and incorporating additional components such as polymers, dECM-based compositions, scaffolds, gels, or membranes can be tailored to match the mechanical, structural, and biochemical requirements of a specific tissue or organ.
[0097] Referring to the accompanying drawings, an embodiment of the present disclosure is shown. This embodiment provides a composition for tissue regeneration in a subject, comprising: a xenogeneic decellularized extracellular matrix (dECM) component containing a biomaterial and a polymer component, wherein the composition is prepared by a method comprising:
[0098] (i) isolating tissue from a donor animal to obtain biological material;
[0099] (ii) decellularizing the biomaterial to obtain a decellularized extracellular matrix component; and
[0100] (iii) combining the decellularized extracellular matrix component with a polymer component to produce a composition with enhanced antimicrobial properties. In some embodiments, the composition is a scaffold, a membrane, or a coating.
[0101] In some embodiments, the donor animal is a goat fetus or goat neonate. In one example, the donor animal is a goat fetus or goat neonate with a gestational age of about 12 weeks to about 18 weeks. In some embodiments, the tissue is selected from one or more fetal membranes or fetal bones from the donor animal, such as fetal membrane tissue and / or fetal bone tissue, such as one or more amniotic membranes and / or chorionic membranes and one or more cortical bones and / or cancellous bones, respectively.
[0102] Figures 1A to 1C Shown is a goat fetal membrane (ACM) where the epithelial layer as well as blood residues were removed by a cell scraper prior to a washing step.
[0103] Figures 26A to 26D shows that after removing muscle, fat and skin ( Fig.26A , 2600) after being cut into small pieces using surgical tools ( Fig.26B , 2610), and then ground into small particles for decellularization ( Fig.26C , 2620). Fig.26D 2630 shows the decellularized extracellular matrix component 2630 of fetal goat bone after freeze drying.
[0104] In an exemplary embodiment, the decellularized extracellular matrix component is present in the form of a powder, a hydrogel, a scaffold, a membrane, a film, a coating or a combination thereof. In certain embodiments, before applying the grinding method to avoid destroying the dECM, for example, liquid nitrogen can be used to cool the dECM to reduce the temperature of the tissue. After or during the grinding process, the dECM can be washed with water or a water-based solution and / or a detergent rinse paper towel. Before being placed in the grinder container, the dECM can be immersed in liquid nitrogen for rapid freezing and freeze drying. The grinding of the tissue can be carried out for at least about 5 seconds, about 10 seconds, about 15 seconds, about 20 seconds, about 25 seconds, about 30 seconds, about 35 seconds, about 40 seconds, about 45 seconds, about 60 seconds, about 90 seconds, about 120 seconds, wherein, after a time interval, for example, about 5 seconds, 10 seconds or 15 seconds, the ground sample can be immersed in liquid nitrogen again to avoid the dECM protein from being destroyed by the heat generated by the grinder. In some embodiments, the dECM produced by the ACM tissue can be digested in a pepsin solution (e.g., about 1 mg to about 2.5 mg or about 2 mg per mL of 0.01 M hydrochloric acid, HCl) for about 24 hours to about 72 hours or about 48 hours with stirring at room temperature (e.g., about 18°C to about 25°C). The resulting digest can be neutralized using an alkali and isotonic buffer (e.g., 10X phosphate buffered saline (PBS), saline, 3-(N-morpholino)propanesulfonic acid (MOPS), HEPES or Hank's balanced salt solution). In some embodiments, the neutralized tissue can be quickly frozen and freeze-dried. In some embodiments, the tissue can then be sterilized, for example, by ultraviolet light.
[0105] Figures 2A to 2C It shows the value before grinding ( Figure 2A ), after grinding ( Figure 2B ) and images of freeze-dried decellularized extracellular matrix component 200 digested with pepsin.
[0106] The composition has enhanced antimicrobial properties that are inherent to and result from the decellularized extracellular matrix component 200, polymer component 300, 500, or a combination thereof. For example, the enhanced antimicrobial properties result from the composition and / or surface morphology of the decellularized extracellular matrix component 200 and / or polymer component 300, 500, and advantageously provides a composition that does not require the administration or inclusion of antibiotic agents in the composition, thereby reducing the risk of using high doses of chemicals and antibiotics that may cause or promote toxicity and the development of antimicrobial resistance.
[0107] In some embodiments, the surface morphology of the decellularized extracellular matrix component 200 and / or the polymer component 300, 500 is porous, smooth, nano-patterned, or a combination thereof. In a preferred embodiment, the nano-patterned surface morphology of the decellularized extracellular matrix component 200 and / or the polymer component 300, 500 provides enhanced antibacterial properties to the composition. In some embodiments, the decellularized extracellular matrix component 200 and / or the polymer component 300, 500 comprises a closely packed array of nanocones. Figure 5B 510 and 5C 520 show closely packed nanopyramids 520, Figure 5B 510 and 5C 520 show arrays made from stretchable filaments stretched over polymer component 500 .
[0108] In another embodiment, polymer components 300, 500 are derived from one or more natural polymers. In one example, polymer components 300, 500 are silk fibroin, chitosan or a combination thereof. When polymer components 300, 500 are fibroin, fibroin is a stretchable film or a rigid film. When polymer components 300, 500 are chitosan, chitosan is pure chitosan or functionalized chitosan. In one example, functionalized chitosan is produced by mixing chitosan with N-(β-maleimido propoxy) succinimide ester at room temperature for about 6 hours.
[0109] Figure 3A and 3B Chitosan is shown as the polymer component 300. These images illustrate the gelation behavior of BMPS-modified chitosan hydrogels combined with dACM particles ("BMPS-dACM" hydrogel 300). The hydrogel solution is liquid at 25°C and is injectable ( Figure 3A ), while after incubation at -20 °C for 24 h, it can be cross-linked and become a stable hydrogel ( Figure 3B ).
[0110] In another embodiment, the polymer component 300, 500 is a membrane, a scaffold, a hydrogel, or a combination thereof.
[0111] In a preferred embodiment, the composition is applied to the skin or bone tissue of a subject in need of tissue repair. In one example, when the skin in need of repair is injured or burned skin, the wound is a chronic wound, an infected skin wound, or a combination thereof. The composition disclosed herein is beneficial for promoting and / or accelerating the repair of damaged or defective bone tissue or injured skin, and has effective antibacterial properties.
[0112] Another embodiment of the present disclosure provides a method for preparing a decellularized extracellular membrane (dECM) composition for tissue regeneration in a subject, the composition comprising a decellularized extracellular matrix (dECM) component and a polymer component. The method comprises the following steps:
[0113] (i) obtaining target tissue from a donor animal;
[0114] (ii) decellularizing the target tissue and removing genetic material from the target tissue to obtain a decellularized extracellular matrix component; and
[0115] (iii) combining the decellularized extracellular matrix component with a polymer component to produce a composition with enhanced antimicrobial properties.
[0116] In a preferred embodiment, the target tissue is selected from one or more fetal membranes or fetal bones. Fetal membrane tissue includes one or more of amniotic membranes and / or chorionic membranes. In certain embodiments, the bone is cancellous bone or cortical bone or a combination thereof, which is obtained from femur\tibia or a combination thereof.
[0117] In an exemplary embodiment, the donor animal is a goat fetus or a goat neonate. Preferably, the donor animal is a goat fetus or a goat neonate with a gestational age of about 12 weeks to about 18 weeks.
[0118] When isolating the target tissue, in some embodiments, the frozen tissue can be thawed overnight at 4°C. In some embodiments, blood residues and epithelial layers can be separated and processed by, for example, a cell scraper. In some embodiments, skin, muscle, fat, and any other tissue except bone can be separated and processed by surgical tools.
[0119] In some embodiments, decellularizing the target tissue comprises: treating the target tissue with a chemical reagent, wherein the chemical reagent comprises a detergent, an enzyme, a chelating agent, or a combination thereof. In one example, the detergent is Triton-x, the enzyme is DNase, and the chelating agent is EDTA. In one example, when decellularizing the target tissue, the tissue is incubated in a buffer, such as a hypotonic Tris buffer (e.g., 10 mM HEPES, pH 7.9, containing 1.5 mM MgCl 2 and 10 mM KCl; 20 mM Tris-HCl, pH 7.4, containing 10 mM NaCl and 3 mM MgCl; 10 mM HEPES, pH 7.5, containing 10 mM MgCl 2and 20 mM KCl; or 5 mM Tris-HCl, pH 7.4, containing 3 mM EDTA), and optionally antibiotics (such as 1% penicillin-streptomycin), chelators (such as ethylenediaminetetraacetic acid (EDTA, 0.1% w / v) or 1,10-phenanthroline) and a protease inhibitor cocktail (e.g., at a concentration of about 2.95 μl / mL). In some embodiments, the incubated ACM tissue can then be washed in an isotonic buffer (e.g., Tris-buffered saline (TBS, pH about 7.6), phosphate-buffered saline (PBS), or N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid (HEPES)), optionally containing an ionic detergent (e.g., sodium dodecyl sulfate (SDS, 1% w / v), Triton X-100, Triton X-200, sulfobetaine-10 and -16, Tween 80, or 3-((3-cholamidopropyl)dimethylammonio)-1-propanesulfonate (CHAPS)), a chelating agent (e.g., EDTA (0.1% w / v) or 1,10-phenanthroline), a protease inhibitor cocktail (e.g., at a concentration of about 2.95 μl / mL), and an antibiotic (e.g., 1% penicillin-streptomycin) using a shaking incubator at about 250 rpm and room temperature for about 4 h to about 72 h or about 24 h. In some embodiments, the ACM tissue can be washed at least 1, 2, 3, 4, or more times with an isotonic buffer (e.g., PBS, HEPES, or TBS) at about 7.6 until the bubbles in the buffer are eliminated. In some embodiments, the ACM tissue can be washed with a hypotonic lysis buffer, e.g., Tris-HCl (e.g., at a concentration of about 50 mM), about 10 mM magnesium chloride (MgCl 2 ) and 50 μg / mL bovine serum albumin, pH about 7.5 to about 7.6, optionally supplemented with DNase (e.g., DNase I at a concentration of about 100 U / mL), RNase (e.g., RNase A at a concentration of about 2 U / mL) and antibiotics (e.g., 1% penicillin-streptomycin). At 250 rpm and 37° C. for about 30 minutes to about 12 hours or about 3 hours. In some embodiments, the hypotonic buffer can be 10 mM HEPES, pH 7.9, containing 1.5 mM MgCl 2and 10 mM KCl; 20 mM Tris-HCl, pH 7.4, containing 10 mM NaCl and 3 mM MgCl; 10 mM HEPES, pH 7.5, containing 10 mM MgCl2 and 20 mM KCl; or 5 mM Tris-HCl, pH 7.4, containing 3 mM EDTA. In some embodiments, after removing the previous buffer, the tissue can be washed with an isotonic buffer (e.g., PBS, HEPES, or TBS) from about 2 to about 5 times or about 3 times. In some embodiments, TBS can be removed and the ACM tissue can be resuspended in sterile MilliQ H 2 O, producing a decellularized extracellular matrix (dECM).
[0120] In another embodiment, decellularizing the target tissue comprises the steps of:
[0121] (i) washing the tissue in a hypotonic buffer optionally supplemented with antibiotics, chelators, and a protease inhibitor cocktail;
[0122] (ii) washing the tissue in an isotonic buffer, wherein the isotonic buffer optionally contains a detergent, a chelating agent, a protease inhibitor cocktail, and an antibiotic;
[0123] (iii) washing the tissue with isotonic buffer;
[0124] (iv) washing the tissue in a hypotonic buffer; and
[0125] (v) Washing the tissue with an isotonic buffer and removing the genetic material from the target tissue to obtain a decellularized extracellular matrix component.
[0126] In one example, decellularizing the target tissue includes the optional step of physically disrupting the target tissue by freeze-thaw, grinding, homogenization, osmotic shock, or a combination thereof. This disrupts cell membranes in the tissue and releases cellular components.
[0127] In some embodiments, the dECM produced by the ACM tissue can be digested in a pepsin solution (e.g., about 1 mg to about 2.5 mg or about 2 mg per mL of 0.01M hydrochloric acid, HCl) for about 24 hours to about 72 hours or about 48 hours at room temperature (e.g., about 18°C to about 25°C) with stirring. The resulting digest can be neutralized using an alkali and isotonic buffer (e.g., 10X phosphate buffered saline (PBS), saline, 3-(N-morpholino) propanesulfonic acid (MOPS), HEPES or Hank's balanced salt solution). In some embodiments, the neutralized tissue can be quickly frozen and freeze-dried. In some embodiments, the tissue can then be sterilized, for example, by ultraviolet light.
[0128] In some embodiments, step (ii) includes a step of reducing the size of the target tissue, such as by grinding the tissue. In some embodiments, during or after washing or freeze drying, the size of the decellularized extracellular matrix components produced by the tissue can be reduced by, for example, grinding. In some embodiments, before applying the grinding method to avoid destroying dECM, liquid nitrogen can be used to cool the dECM to reduce the temperature of the tissue. After or during the grinding process, dECM can be washed with water or a water-based solution and / or a detergent rinse paper towel. Before being placed in a grinder container, dECM can be immersed in liquid nitrogen for rapid freezing and freeze drying. The grinding of the tissue can be carried out for at least about 5 seconds, about 10 seconds, about 15 seconds, about 20 seconds, about 25 seconds, about 30 seconds, about 35 seconds, about 40 seconds, about 45 seconds, about 60 seconds, about 90 seconds, about 120 seconds, wherein, after a time interval, such as about 5 seconds, 10 seconds or 15 seconds, the ground sample can be immersed in liquid nitrogen again to avoid the dECM protein from being destroyed by the heat generated by the grinder.
[0129] In an exemplary embodiment, steps (i) to (v) include shaking the target tissue at about 100 rpm to about 250 rpm. In another exemplary embodiment, step (i) is performed at room temperature for about 4 hours to about 72 hours, and step (v) is performed at 37°C for about 30 minutes to about 12 hours.
[0130] In certain embodiments, polymer component 300,500 derives from one or more natural polymers, including silk-fibroin, chitosan or its combination.Silk-fibroin is, for example, a stretchable film or a hard film.Chitosan is, for example, pure chitosan or functionalized chitosan.In an exemplary embodiment, polymer component is a functionalized chitosan produced by mixing chitosan with N-(β-maleimido propoxy) succinimide ester for about 6 hours at room temperature.
[0131] The polymer component 300, 500 is a membrane, a scaffold, a hydrogel, or a combination thereof, and the surface morphology of the polymer component 300, 500 is porous, smooth, nano-patterned, or a combination thereof.
[0132] In some embodiments, the decellularized extracellular matrix component 200, 2630 is present in the form of a powder, solution, hydrogel, scaffold, membrane, film, coating or a combination thereof. In addition, the surface morphology of the decellularized extracellular matrix component 200, 2630 is porous, smooth, nano-patterned or a combination thereof.
[0133] The nanopatterned surface morphology of the decellularized extracellular matrix component and / or polymer component provides enhanced antimicrobial properties to the decellularized extracellular membrane (dECM) composition, thereby providing a decellularized extracellular membrane (dECM) composition having antimicrobial and anti-inflammatory properties and optimal mechanical properties. The decellularized extracellular membrane (dECM) composition is a scaffold, membrane or coating that can be applied to the skin or bone tissue of a subject in need of tissue repair.
[0134] In some embodiments, the present disclosure relates to the use of dECM for the manufacture of antimicrobial biostructures. In one embodiment, the present disclosure provides compositions and methods of preparing the same for wound healing purposes (e.g., in diabetic patients). In some embodiments, the present disclosure provides compositions and methods of preparing the same for bone regeneration purposes.
[0135] In some embodiments, the present disclosure provides dECM-based medical devices with improved antimicrobial and biological properties for tissue regeneration and healing applications, comprising a decellularized extracellular matrix component and a polymer component.
[0136] It will be appreciated by those skilled in the art that various changes and / or modifications may be made to the present disclosure as shown in the specific embodiments without departing from the spirit or scope of the present disclosure as broadly described. Therefore, the present embodiments are to be considered in all aspects as illustrative and not restrictive.
[0137] Unless otherwise indicated, any reference to prior art contained herein should not be taken as an admission that the information is common general knowledge.
[0138] Example
[0139] Materials and Methods
[0140] Fetal membrane dECM
[0141] The fetal membrane is a thin, two-layer structure, including the amnion and the chorion, that surrounds the developing fetus during pregnancy. The amnion and chorion are separate and have different roles during pregnancy. While the amnion covers the embryo and holds the amniotic fluid, the chorion surrounds the amnion, embryo, and other membranes, which act as a protective barrier during fetal development.
[0142] The amniotic membrane is a gelatinous avascular matrix without nerves and lymphatic vessels closest to the fetus. It consists of three layers, including an epithelial layer, a basal layer, and an avascular stromal layer, which in turn consists of a dense layer, fibroblasts, and a spongy layer connected to the chorion. In most existing studies, the basement membrane of the amniotic membrane has been used for most tissue engineering applications. The membrane is mainly composed of collagen, which provides structural integrity and mechanical strength to the tissue. In addition to type III, IV, and V collagens, non-collagenous glycoproteins are also present in its structure, including fibronectin, laminin, and nestin. A series of growth factors can be found in the amniotic membrane, such as keratinocyte growth factor (KGF), epidermal growth factor (EGF), basic fibroblast growth factor (bFGF), transforming growth factor (TGF)-α, -β1, -β2 and -β3, KGF receptor (KGFR), hepatocyte growth factor (HGF), HGF receptor (HGFR), platelet-derived growth factor (PDGF) and vascular endothelial growth factor (VEGF).
[0143] The chorion is the outer layer of the fetal membrane, which is also in contact with maternal cells and consists of three layers: a) a reticular layer made of collagens I, III, IV, V and VI and proteoglycans, b) a basement membrane containing collagen IV, fibronectin and laminin, and c) a trophoblast. Both the chorion and the amnion contain different amounts of cytokines and growth factors, as shown by the proteomic evaluation of the amnion and the chorion. For example, PDGF-AA and PDGF-BB were detected in chorion factors such as adiponectin, angiopoietin-2, bFGF, endocrine gland-derived vascular endothelial growth factor (EG-VEGF), HGF, insulin-like growth factor (IGF-1), (tissue inhibitor of metalloproteinases) TIMP-2 and TIMP-4. Therefore, the fetal membrane and its derivatives, the amnion, the chorion have been used to prepare biomaterials for more than 100 years, which are used for many tissue engineering and regenerative medicine purposes. Human amniotic membrane is very popular in ophthalmology for ocular surface reconstruction or corneal replacement, for the treatment of chronic wounds and burns, or as a skin substitute in dermatology. In addition, although its use is not as common as amniotic membrane, human amniotic-chorionic membrane (ACM) still shows promising results in wound healing applications.
[0144] Fetal membranes are useful for wound healing applications due to the presence of proteins and growth factors in their ECM. ACMs generally protect the fetus from pathogens that can cause dangerous pregnancy complications (including premature rupture of membranes and premature birth). One of the potential mechanisms for this protection is that their structure is impermeable to pathogens. In addition, the presence of antimicrobial peptides (AMPs) expressed by cells in the membrane directly affects the available microorganisms in amniotic fluid and ACM. AMPs are a group of small proteins that are secreted by some immune and epithelial cells and play an important role in the innate immune system. They provide antibacterial, anti-inflammatory, antifungal, antiviral, antifibrotic and analgesic effects and regulate cell differentiation and angiogenesis, all of which are particularly critical in the wound healing process.
[0145] Amniotic growth factors, such as TGF-β and EGF, stimulate the migration of keratinocytes. During the proliferation phase of wound healing, the secreted factors stimulate keratinocytes and fibroblasts. They can also affect the migration of keratinocytes that lead to wound re-epithelialization. In addition to this, it can regulate angiogenesis due to its anti-angiogenic and pro-angiogenic properties. Moreover, during the remodeling phase, it promotes wound contraction and scar formation.
[0146] Despite the many advantages of human amniotic membrane, its use is limited by a number of factors. These factors include: (1) human amniotic membrane is scarce and its use is extremely expensive, (2) it has weak mechanical properties, (3) it can cause infectious diseases, and (4) religious concerns hinder its widespread use. Therefore, we addressed these limitations by selecting xenogeneic fetal membrane dECMs, enabling large-scale production while providing regenerative properties for wound healing purposes.
[0147] Decellularization of goat fetal membranes
[0148] Frozen fetal goat membrane (ACM) was thawed overnight at 4°C, and blood residues and the epithelial layer were gently removed using a cell scraper ( Figures 1A to 1C). The membrane was then cut into small pieces and incubated for 16 hours in a hypotonic Tris buffer (10 mM, pH 8) containing ethylenediaminetetraacetic acid (EDTA, 0.1% w / v) and a protease inhibitor cocktail (2.95 μL / mL) and a penicillin-streptomycin-neomycin antibiotic cocktail (PSN, 1%). Subsequently, the tissue was washed for 24 hours with Tris-buffered saline (TBS, pH 7.6) containing sodium dodecyl sulfate (SDS, 1% w / v), EDTA (0.1% w / v), a protease inhibitor cocktail (2.95 μl / mL) and PSN (1%), using a shaking incubator at 250 rpm and room temperature. Next, the tissue was washed several times with TBS, pH 7.6, until the bubbles in the buffer were removed. Then, the samples were washed with a buffer consisting of 50 mM Tris-HCl, 10 mM magnesium chloride, and 50 μg / mL bovine serum albumin at pH 7.5 (supplemented with 100 U / mL DNase I, 2 U / mL RNase A, and 1% PSN) at 250 rpm and 37°C for 3 hours. After removing the previous buffer, the tissue was washed three times with TBS, and finally TBS was exchanged with sterile MilliQH2O. The samples were quickly frozen in liquid nitrogen and freeze-dried ( Figure 2A ).
[0149] Preparation of pepsin-digested fetal membrane dECM particles
[0150] The freeze-dried fetal membrane dECM was ground using a grinder (IKA A11 basic) to reduce the size of the dECM pieces into smaller particles ( Figure 2B ). The dECM pieces were added to the grinder container and immersed in liquid nitrogen for a period of time before grinding to avoid the destruction of the dECM protein due to the heat generated during the grinding process. Then, 20 mg of the dried ACM dECM powder was digested in a pepsin solution (2 mg in 0.01 M hydrochloric acid, HCl) at room temperature for 48 hours with stirring. Then, the resulting digest ( Figure 2C ) was neutralized on ice with 0.1 M sodium hydroxide (NaOH) and 10x phosphate buffered saline (PBS), then snap frozen and freeze dried. The resulting powder was UV sterilized prior to use in in vitro and animal studies.
[0151] Chemical functionalization of chitosan
[0152] To improve the antimicrobial properties of chitosan, a maleimide-NHS ester crosslinking reagent called N-(β-maleimidopropyloxy) succinimide ester (βMPS) was used to chemically functionalize chitosan chains to endow them with maleimide groups. βMPS is a water-insoluble heterobifunctional protein crosslinker with thiol and amine reactive groups. Spacer arm connection. Through its NHS-ester, βMPS can be conjugated (or labeled) with primary amines of proteins, amine-modified oligonucleotides or other amine-containing molecules, while through its maleimide group, it reacts with substances or biomolecules with thiol groups and forms covalent bonds. Here, βMPS is directly coupled to chitosan amino groups through amide formation, so that the degree of chemical modification of chitosan is controlled. In addition to the above mechanism, the remaining chitosan amino groups further react with the maleimide groups provided by βMPS through Michael addition, which proceeds mildly without forming by-products. As a result of the chemical reaction, βMPS-chitosan can be used as a scaffold. Not only is βMPS-chitosan capable of self-crosslinking, but it also has improved antibacterial properties compared to non-functionalized chitosan. In order to chemically functionalize chitosan with βMPS, chitosan oligosaccharides with a molecular weight of MW = 5 to 10 kDa, Cat.No.P312015, were dissolved in heated PBS (pH 7.4) at a concentration of 4% w / v. Subsequently, the solution was centrifuged at 7800 rpm for 20 minutes to remove undissolved powder, and the supernatant was filtered using 0.45 and 0.22 μm syringe-driven filters in sequence. After the pH was adjusted to 7.0 by NaOH solution (1 M), 4 mL of βMPS solution in dimethylformamide (308.59 mM) was gradually added dropwise to the chitosan solution, while the solution was thoroughly mixed at 1000 rpm using a magnetic stirrer. After stirring at room temperature for 6 hours, the resulting solution was filtered using 0.45 μm and 0.22 μm syringe-driven filters, and then dialyzed in ultrapure water for 3 days using dialysis bags (MWCO: 3.5 kDa) in sequence. Subsequently, the solution was concentrated by a centrifugal filter (3 kDa MWCO) to adjust the final chitosan concentration to 3% w / v. Next, the solution impurities were removed by a 0.22 μm filter, and the resulting βMPS-chitosan solution was quickly frozen by liquid nitrogen and kept at -80 ° C.
[0153] Preparation of chitosan-based hydrogels
[0154] To make non-functionalized chitosan hydrogels, β-glycerophosphate (β-GP) was dissolved in ultrapure water and mixed with pure oligomeric chitosan solution in PBS as a physical crosslinker, with the concentrations of oligosaccharides and β-GP being 3% w / v and 14.2 wt.%, respectively. Subsequently, the mixture was incubated at 37°C for several minutes to form a stable hydrogel. This sample was named "CS". In addition, βMPS-chitosan (chitosan concentration (3% w / v)) was incubated at -20°C for 24 hours to form a stable hydrogel, referred to as "BMPS". Both CS and BMPS were used to study the effects of chitosan chemical functionalization and the use of dACM on the antibacterial properties of chitosan-based gels. To prepare composite hydrogels, βMPS-chitosan (chitosan concentration of 3 w / v%) was mixed with pepsin-digested ACM dECM powder (concentration of 20 mg / mL). After mixing using a vortex mixer, the dECM particles were almost dissolved in the βMPS-chitosan solution and evenly distributed within the chitosan polymer network within a few seconds, thereby obtaining a homogeneous solution. Afterwards, the mixture was incubated at -20 °C for 24 h to form a stable hydrogel ( Figure 3A and 3B ). This sample was denoted as “BMPS-dACM”.
[0155] Preparation of stretchable silk fibroin membrane
[0156] In order to make a stretchable silk fibroin matrix, silk fibroin was first produced. 5 g of silkworm (Bombyx mori) cocoons were cut and then supplemented with sodium carbonate (Na 2 CO 3 , 0.02M) water (2 L) was boiled for 30 minutes to degummed the silk and remove its sericin. The obtained silk was then washed three times with ultrapure water and dried at room temperature. Subsequently, a constant amount of dry silk (1.5 g) was dissolved in 10 g of calcium chloride (CaCl 2 ) in formic acid, CaCl 2 The different ratios of formic acid were 2%, 2.5%, 3% and 5%. After dissolving the silk fibers, residual bubbles were removed by ultrasonic treatment, and then the solution was poured into the desired mold for casting. The casting mold was placed under a fume hood for several days to allow the formic acid in the casting solution to evaporate completely. Next, the silk matrix was separated from the mold and water annealed overnight to properly crosslink the matrix. Subsequently, the substrate was washed with ultrapure water for 30 minutes to remove any formic acid residues on the surface.
[0157] Developing nanopatterns on plasticized silk substrates
[0158] Colloidal lithography was performed on water-annealed silk films with the best mechanical properties, where CaCl 2The ratio of formic acid is 3%. For this purpose, a 2.5w / v% solution of polystyrene nanospheres with a size of 300nm (from the Baseline Chromatography Research Center of Tianjin, China (Product No. 6-1-0030)) is used. A few drops of the original polystyrene solution are centrifuged at 7000rpm for 10 minutes, and the supernatant is then discarded. Subsequently, the polystyrene pellets are dispersed in distilled water and ethanol by ultrasonic treatment for 1 hour to form a 10wt.% solution with a suitable distribution of nanospheres. Then, in order to coat the silk matrix with a hexagonal close-packed array of nanospheres, a clean 10mm diameter petri dish is filled with 20 to 25mL of distilled water. The slide is then placed at a 20° angle to the petri dish. For best results, before use, 10 minutes of O 2 Plasma treatment was performed to increase the humidity of the glass slide. A small drop (1 μL) of the nanoparticle suspension was introduced into the middle of the glass slide. The nanospheres were distributed as a monolayer on the water surface by sliding towards the water surface. The process was repeated until complete nanosphere coverage was obtained on the surface. Subsequently, about 5 μL of SDS (2% w / v) was added to the water to form a tightly packed hexagonal array of nanospheres. The monolayer produced at a shallow angle was used to coat the surface of the silk matrix. The coated sample ( Figure 4 400) was placed in another clean container and dried for further use. The precipitate was prepared by a magnetron sputtering instrument (Phase II J, ATC Orion Sputtering System, AJA International Inc.) with O 2 Plasma etching of the coated nanospheres on the surface for 15 min (at 7 mTorr and 50 W) left the silk substrate nanopatterned structures (nanocones) on the surface ( Figure 5A and 5B ).
[0159] Preparation of wound dressing scaffolds
[0160] To prepare the wound dressing scaffold, a stretchable silk mesh substrate with nanofeatures on its surface was placed into a well plate, and the precursor solution of BMPS-dACM was cast on it and incubated at −20 °C for 24 h to allow it to fully gel.
[0161] Animal fetal bone dECM
[0162] Fetal skin matrix has the ability of scarless healing in early pregnancy without any severe inflammation or a large amount of fibrosis. Therefore, fetal-derived dECM is considered to be a potential candidate for tissue engineering and regenerative medicine applications. Once fetal tissue is damaged, compared with its adult counterpart, its response to damage is accompanied by a larger amount of glycosaminoglycans (GAG) such as hyaluronic acid and chondroitin sulfate, which can promote cell mitosis, migration and differentiation. In addition, compared with the dECM derived from adult counterparts, the dECM derived from fetal tissue contains a larger number of immature collagens and less molecular cross-linking, thereby experiencing rapid degradation and rapid, structural and robust remodeling. Therefore, the dECM obtained from fetal and / or neonatal tissues has different regenerative properties and less antigenicity compared with their adult counterparts, which makes them valuable sources for preparing bioactive materials with enhanced cell reproduction efficiency, substantial regenerative properties and structural tissue remodeling. Therefore, in the disclosure claimed for protection, bone dECM derived from fetal goat bone is used to manufacture an antibacterial membrane, which can substantially regenerate bone while protecting tissue from possible infection at the site of injury.
[0163] Decellularization of fetal goat bone
[0164] Frozen fetal goat limbs were thawed overnight at 4°C to separate the bones from the muscle, skin, fat, and cartilage. Cortical and cancellous bones from the femur and tibia were used for decellularization ( Fig.26A To do this, the bone is cut into small pieces using bone cutters and surgical tools under sterile conditions ( Fig.26B Next, the frozen bone blocks were ground into particles ( Fig.26C ). Then use sterile MilliQ H 2 O was used to wash away blood residues several times. After soaking the bone particles in sterile hypotonic buffer (10 mM Tris-HCl, pH 8.0) for 1 hour, the particles were subjected to several freeze-thaw cycles to disrupt the cells and enhance cell membrane disruption. Next, the wash buffer was changed to TritonX-100 (1%) buffer containing a protease inhibitor cocktail to effectively remove the remaining blood and cell compartments overnight. Subsequently, sterile MilliQ H 2 O to completely remove the detergent. Then, the sample was incubated with a hypertonic buffer Tris-HCl buffer for up to 2 hours, followed by treatment with DNase I (50 U / mL) and RNase A (1 U / mL) at 37°C for at least 4 hours. Then, the sample was washed overnight with a hypotonic buffer supplemented with a protease inhibitor cocktail to remove cell remnants and the nuclease used in the previous step. The sample was then washed with an autoclaved MilliQH 2O wash the bone powder several times and then snap freeze in liquid nitrogen for freeze drying process. The resulting fetal goat bone dECM was kept at -80 °C for later use ( Fig.26D ). Except for the last use of MilliQ H 2 All wash buffers except the O wash cycle were supplemented with 1% antibiotic (PSN or PS), and samples were shaken during the wash steps to facilitate the decellularization process.
[0165] Demineralized fetal goat bone dECM
[0166] Frozen fetal goat limbs were thawed overnight at 4°C to separate the bones from muscle, skin, fat, and cartilage. Cortical and cancellous bones from the femur and tibia were used for decellularization. The bones were cut into small pieces under sterile conditions using bone cutters and surgical tools. Next, the frozen bone blocks were ground into particles using a grinder. Sterile MilliQ H 2 O to wash away blood residues in the fetal goat bone particles. The samples were shaken at room temperature and 250 rpm for 50 minutes. The supernatant was discarded and the washing medium was renewed several times in this step. Thereafter, the bone particles were demineralized using a sterile 10% EDTA solution in PBS while maintaining on a shaker at 150 rpm at room temperature for 24 hours. After discarding the previous buffer, the particles were washed with autoclaved MilliQ H 2 O wash bone samples, and then incubate with hypotonic buffer (10mMTris-HCl, pH8) supplemented with 1% PSN for 2 hours at room temperature with shaking. Subsequently, the wash buffer was renewed, the samples were exposed to freeze-thaw cycles several times, and the buffer was exchanged between each cycle. Next, the wash buffer was changed to 10mM Tris-HCl (pH7.5) supplemented with 3.5% TritonX-100, 1% PSN and protease inhibitor cocktail (2.95μl / mL). The samples were incubated in a shaking incubator at 37°C and 250rpm for 4 hours. Subsequently, the samples were incubated with autoclaved H 2 Wash with O for four cycles to wash away the detergent until no bubbles are detected in the sample.
[0167] Subsequently, the wash buffer was changed to 50 mM Tris-HCl, 1.5 M NaCl, pH 7.6, and the sample was stirred at room temperature for 30 minutes. Then, the supernatant was discarded, and a new wash buffer containing 10 mM Tris-HCl, pH 7.5 supplemented with 1% PSN, DNaseI (50 U / mL) and RNaseA (1 U / mL) was added to the bone particles. This washing step lasted for 5 h at 37 ° C with stirring. Then, a hypotonic buffer (10 mM Tris-HCl, pH 8) was added with a protease inhibitor cocktail (2.95 μl / mL) and 1% PSN for removing cell residues and the nuclease used in the previous step. This cycle lasted for 20 hours at 37 ° C. Thereafter, the bone particles were washed with an autoclaved MilliQ H 2 O wash bone powder for 72 h while shaking the sample at 37 °C and frequently renew the wash medium during this step. Decellularized bone particles were snap frozen in liquid nitrogen and kept at -80 °C overnight before freeze drying. The resulting demineralized fetal goat bone dECM was kept at -80 °C for later use.
[0168] To dissolve the demineralized fetal goat bone dECM, the powder was digested in pepsin (2 mg / mL) acidic solution (0.01 M HCl) for 96 hours. The concentration of the demineralized fetal goat bone dECM powder in the acidic solution was adjusted to 10 to 11 mg / mL and kept at 4°C until use.
[0169] Preparation of dECM-silk fibroin membrane
[0170] To make the bone dECM-based membrane, silk fibroin was used. 5 g of silkworm (Bombyx mori) cocoons were cut open and placed in a solution supplemented with sodium carbonate (Na 2 CO 3, 0.02M) in water (2 liters) and boiled for 30 minutes to degummed the silk. Then, the resulting silk was washed three times with ultrapure water and then immersed in LiBr (lithium bromide, 9.3M) to completely dissolve. Next, the resulting dissolved silk solution was dialyzed with ultrapure water for 48 hours. Subsequently, the resulting solution was centrifuged at 10000rpm for 20 minutes at 4°C twice to remove impurities. Then, after neutralizing its pH to 7.4 using NaOH (1M), it was mixed with the digest of demineralized fetal goat bone dECM, wherein the volume ratio of silk fibroin solution to bone digest included 4:1, 3:2, 1:1, 2:3, 1:4. Subsequently, the blend (8mL each) was cast in a Petri dish (60mm) and placed under a range hood until completely dry. Next, the membrane was peeled off the mold and water annealed for cross-linking. The resulting dry membrane was named "non-reinforced fetal bone dECM-silk membrane". The hybrid composite membranes were further prepared using fetal goat bone dECM using the optimized ratio of the blend (1:1). Different amounts of bone dECM powder (1, 2, or 3% w / v) with a size equal to or less than 200 μm were mixed with the blend using a vortex mixer before casting. Subsequently, the same procedure described above for the preparation of non-enhanced bone dECM-silk membranes was performed. The resulting membranes were named "fetal bone dECM-silk hybrid composite membranes".
[0171] Developing nanopatterns on dECM-silk membranes
[0172] Colloidal lithography was performed on water-annealed fetal bone dECM-silk membranes with optimal mechanical properties (unreinforced fetal bone dECM-silk membranes with a ratio of silk to dECM bone digest of 1:1, which was referred to as "unreinforced dECM-silk (1:1)") and fetal bone dECM-silk hybrid composite membranes containing 2% w / v dECM bone particles, which was referred to as "2% dECM-silk hybrid composite materials"). For this purpose, a 2.5 w / v% solution of polystyrene nanospheres with a size of 300 nm (from Baseline Chromatography Research Center, Tianjin, China (Product No. 6-1-0030)) was used. A few drops of the original polystyrene solution were centrifuged at 7000 rpm for 10 minutes, and the supernatant was discarded. Subsequently, the polystyrene pellets were dispersed in distilled water and ethanol by ultrasonic treatment for 1 hour to form a 10 wt.% solution with a suitable distribution of nanospheres. Then, to coat the silk substrate with a hexagonal close-packed array of nanospheres, fill a clean 10 mm diameter Petri dish with 20 to 25 mL of distilled water. Then place the slide at a 20° angle to the dish. For best results, heat the silk substrate with 10 min of O before use. 2Plasma treatment to increase the humidity of the slide. A drop of 1 μL of the nanoparticle suspension was introduced into the middle of the slide. By sliding towards the water surface, the nanospheres were distributed on the water surface as a monolayer. The process was repeated until complete nanosphere coverage was obtained on the surface. Subsequently, about 5 μL of SDS (2% w / v) was added to the water to form a tightly packed hexagonal array of nanospheres. The monolayer produced at a shallow angle was used to coat the surface of the silk matrix. The coated sample was then placed on another clean container and dried for further use. The sample was precipitated by a magnetron sputtering instrument (Phase II J, ATC Orion Sputtering System, AJA International Inc.) with O 2 The coated nanospheres on the surface were plasma etched for 15 minutes (at 7 mTorr and 50 W) leaving silk-based nanopatterned structures (nanocones) on the surface.
[0173] The experiments described below provide further examples of the use of the dECM-based compositions with antimicrobial properties claimed in the present disclosure for tissue regeneration and wound healing. The present disclosure advantageously promotes the healing of tissues in need of repair while reducing the risk of post-operative infection at the site of injury.
[0174] Example I - Preparation of a dECM-based wound dressing with antimicrobial properties for promoting chronic wound healing in diabetic mice
[0175] Potential applications
[0176] Experiments were designed to fabricate antimicrobial wound dressing composites with high potential for clinical application in promoting chronic wound healing in diabetes.
[0177] Embodiments of the present disclosure include decellularization of goat fetal membranes to prepare soluble dECM powders / particles, functionalization of chitosan amine chains with maleimide groups with improved antibacterial resistance compared to pristine chitosan, and preparation of nanopatterned stretchable silk fibroin matrices.
[0178] DNA content analysis
[0179] The residual DNA in the ACMdECM obtained by the method of Example 1 was quantified and compared with the residual DNA in the non-decellularized tissue as a control. The samples were digested at 56°C using the digestion buffer and proteinase K provided in the DNA extraction kit (DNeasy blood and tissue kit, QIAGEN). Subsequently, the DNA in the digested tissue was purified using the kit according to the manufacturer's protocol and purified by Qant-iT according to the provided protocol. TM The purified DNA obtained in each sample was measured by a dsDNA quantification kit. Experiments were performed in triplicate. Figure 7 The results shown in 700 demonstrate that the DNA content of the dECMs was significantly reduced by 99.62% compared to the control ACMs, thus making them cell-free ACM ECMs devoid of cellular debris.
[0180] In order to confirm the effective cell removal and collagen preservation in the dECM of ACM, the samples produced by the decellularization method of Example 1 were subjected to hematoxylin and eosin (H&E) staining and trichrome staining, and the stained sections were evaluated by optical microscopic observation. In the black and white images of H&E staining, the cell nuclei appear as black dots, while the cytoplasm and ECM appear in gray, as shown in FIG. Fig. 8A 800 and 8B 810. In the black and white images of trichrome staining, collagen fibers appear in gray, while cell nuclei appear as black dots (as shown in FIGS. 9A 900 and 9B 910). As shown in FIGS. 8A 800 to 8B 810 and 9A 900 to 9B 910, the decellularization method of Example 1 can remove cells from the ACM structure quite well, leaving the collagen well preserved.
[0181] Hydroxyproline assay
[0182] The total collagen content of control and decellularized fetal goat ACM was quantified using a hydroxyproline assay kit (ab222941) according to the manufacturer's protocol. The results showed that when the decellularization method of Example 1 was used, the collagen content of ACM did not change significantly, as shown in Fig.10 1000 as shown.
[0183] Atomic force microscopy (AFM) analysis
[0184] The compressive elastic modulus of the stretchable silk substrate of Example 1 was measured by the Hertz model as described above based on the force-displacement curves obtained by atomic force microscopy (AFM) analysis. Three AFM studies were performed on samples stored in a desiccator or in standard atmospheric pressure (not dried). The best sample (containing 3% CaCl) for preparing the final wound dressing scaffold was also tested in the wet state. 2 to formic acid ratio) to evaluate its mechanical properties under wet / humid conditions, which are more relevant to its practical application on wounds. Fig.11A The results shown in 1100 and 11B 1110 indicate that the stretchable silk matrix has a higher compressive elastic modulus if kept in a desiccator compared to normal atmospheric pressure. In addition, increasing the CaCl 2 The ratio of formic acid to 3% CaCl significantly decreased the compressive elastic modulus. 2The wetted silk matrix with formic acid ratios showed compressive elastic moduli of 4.374 ± 0.28 and 0.63692 ± 0.10 MPa, respectively. Fig.12 1200. This indicates that once kept in wet conditions, the polymer film loses stiffness and becomes softer. However, as more CaCl is removed from the surface 2 Leading to a stiffer substrate, the introduction of nanocones on the surface increased the elastic modulus.
[0185] Bacteria research
[0186] In vitro antibacterial properties
[0187] In these evaluations, two bacterial strains were used: Staphylococcus aureus (S.aureus) (ATCC29213) and Pseudomonas aeruginosa (P.aeruginosa). The bacteria were cultured overnight in a lysogenic broth (LB) medium in an oscillating incubator at 220 rpm and 37 ° C. The bacterial optical density (OD) was adjusted to 0.1 (OD600 = 0.1) by supplementing a suitable fresh medium for reactivation for 3 hours. In order to evaluate the antibacterial properties of the samples, the ACM dECM powder and silk matrix were UV sterilized before the experiment, while the chitosan hydrogel was sterilized through a 0.22 μm filter. Next, the antibacterial effects of chitosan oligosaccharides, chitosan βMPS functionalization, ACMdECM, silk and nano-patterned silk matrices (both prepared by 3% CaCl2 and formic acid ratio) were tested using sterilized samples including CS, BMPS, BMPS-dACM, silk and nano-patterned silk matrices. To this end, the sterilized samples were added to a 24-well plate and 100 μL of a 10 5 CFU / mL of diluted bacterial solution was cultured on the surface of each sample for 1, 3, 6 and 24 hours. At the same time, the gaps between the wells of the well plate were filled with sterile water to avoid evaporation of the culture medium. At the above time points, the attached bacteria were separated from the sample by adding 900 μL of culture medium to each well and pipetting up and down. Next, appropriate dilutions of the bacterial suspension were used at each time point and spread on solid agar plates and cultured for another 16 hours to count the co-calibrated CFU. Antibacterial determination of the sample The antibacterial rate of the sample:
[0188]
[0189] As a control for the antibacterial activity of silk or chitosan samples, wells of a 24-well plate were used to culture bacteria and the experiment was performed at each time point under the same conditions.
[0190] As shown in Figures 131300 and 141400, chemical functionalization of chitosan oligosaccharides with βMPS improved the antibacterial efficiency of the original chitosan hydrogel (CS) against Staphylococcus aureus. Staphylococcus aureus showed the best antibacterial performance when ACM dECM was incorporated into the functionalized chitosan gel. The effect of chitosan βMPS functionalization on improving the antibacterial performance of the original chitosan against Pseudomonas aeruginosa can be seen in Fig.15 1500.
[0191] Fig.16 1600 and 17 1700 show photos of agar plates of Staphylococcus aureus. Staphylococcus aureus and Pseudomonas aeruginosa were cultured for 1, 3, 6 and 24 hours respectively after treatment with silk and nanopatterned silk in the wells of a 24-well plate as a control. The results confirmed that the nanocones on the surface of the stretchable silk matrix interacted with Staphylococcus aureus and Pseudomonas aeruginosa, which significantly improved the antibacterial properties of the original silk film. While silk has a certain antibacterial effect on Pseudomonas aeruginosa, the introduction of nano on its surface can significantly increase its antibacterial rate.
[0192] Adhesion testing of stretchable silk films
[0193] The same composition (CaCl) with and without nanopatterns 2 Stretchable silk films prepared with 3% formic acid (ratio of 1% to 3%) were used for bacterial adhesion testing. Samples were UV sterilized in a biosafety cabinet before the experiment. Two bacterial strains were used in these evaluations: Staphylococcus aureus and Pseudomonas aeruginosa. The bacteria were cultured overnight in LB medium in a shaking incubator at 220 rpm, 37°C. The bacterial optical density was adjusted to 0.1 (OD600 = 0.1) by supplementing with appropriate fresh medium for reactivation for 3 hours. To evaluate bacterial adhesion, the bacterial concentration was adjusted to 10 5 CFU / mL, and 100 μL of the solution was spread on the substrate surface to simulate immersion. At different time points (1, 3, 6 and / or 24 hours), the culture medium was removed and the substrate was fixed with 2.5% glutaraldehyde overnight. Afterwards, the samples were washed with 10%, 30%, 50%, 75% and 96% ethanol in sequence and dried at 25°C before being observed with SEM ( Figures 18A to 18D , 19A to 19D, 20A to 20D, 21A to 21D). The results confirmed that the nanocones on the surface interacted with Staphylococcus aureus and Pseudomonas aeruginosa, significantly affected their morphology compared to their counterparts without nanofeatures (filaments), and inhibited the adhesion and formation of biofilms on the nanopatterned surfaces.
[0194] Animal studies
[0195] All experiments were approved by the Animal Research Ethics Committee of the Chinese University of Hong Kong (reference number 22-364-HMF). All db / db mice were purchased from the Animal Center of the Chinese University of Hong Kong with animal research ethics approval. Mice were maintained at a controlled temperature of approximately 20°C with a 12-h light / 12-h dark cycle, free access to water, and a pelleted commercial diet.
[0196] The full-thickness skin defect mouse model was established as follows: Under general anesthesia and aseptic conditions, 6-week-old db / db mice (male, average weight 32.2 g ± 2.4 g) were used. Two parallel 6 mm circles (surface area 28.26 mm 2 ) Full-thickness skin wounds. A polyethylene collar was sutured to the adjacent skin to hold each wound edge.
[0197] Animal Group
[0198] To examine the effects of different samples on wound healing after surgery for diabetic full-thickness skin defects, db / db mice were randomly divided into 5 groups (n=6 per group). Wounds were treated with 1) none (NC group) or hydrogel scaffolds; 2) CS; 3) BMPS; 4) BMPS-dACM and 5) ChitoSilk BioPatch. The width of the scaffold in each group was adjusted according to the diameter of the wound size (6 mm). Wound images were collected on days 0, 3, 7, 10 and 14 after surgery. The splint was removed 7 days after surgery. Skin wound samples were collected on days 7 and 14 after surgery, and tissue regeneration was evaluated by histological analysis and immunofluorescence staining.
[0199] Histological analysis
[0200] Different groups of mice were killed with overdose (7 and 14 days after surgery), and wound samples including full thickness skin layers (epidermis, dermis and subcutaneous tissue) were fixed in 4% buffered paraformaldehyde and embedded in paraffin. 7 μm tissue sections were stained with H&E and photographed by Leica image analysis system. 7 μm thick tissue sections treated with Sirius Red were photographed by polarizing microscope. Images were captured at 100 times with Leica DM 5500 system.
[0201] Immunofluorescence staining
[0202] 7 μm tissue sections were subjected to immunofluorescence double labeling staining. Briefly, after antigen retrieval, anti-F4 / 80 (1:200; ab6640, Abcam, USA), anti-iNOS (1:200; ab15323, Abcam, USA), anti-CD206 (1:200; ab64693, Abcam, USA), anti-CD31 (1:200; ab182981, Abcam, USA), anti-α-SMA (1:200; ab7817, Abcam, USA) were used, and tissue sections were incubated with primary antibodies at 4 °C for 16 hours. Then, the sections were incubated with secondary antibodies Alexa488 (1:500 dilution; ab150077, Abcam, USA) or Alexa594 (1:500 dilution; ab150160, Abcam, USA) for 1 hour at room temperature. Cell nuclei were stained with ProLong Diamond Antifade DAPI (Life Technologies, USA). Images were acquired at 200× using a Leica DM 5500 system and analyzed using Image Pro Plus 6.0.
[0203] Ethical Statement
[0204] Animal studies were performed under an animal permit issued in Hong Kong, China and approved by the Animal Experimentation Ethics Committee of the Chinese University of Hong Kong (reference number 22-364-HMF).
[0205] Statistical analysis
[0206] All experiments were repeated at least 3 times. The results are expressed as mean ± standard deviation. The statistical significance of the results was evaluated by one-way analysis of variance, and the significance level was set at p < 0.05 (*).
[0207] The biocompatibility and bioactivity of ChitoSilk BioPatch were evaluated using the chronic wound model established with db / db mice. Full-thickness skin wounds (diameter: 6 mm) were located on the back of db / db mice and subsequently covered with CS, BMPS, BMPS-dACM, ChitoSilk BioPatch, or no coverage (control group, NC). Wound healing outcomes were examined by visual observation and histological evaluation with H&E and Sirius red staining. On and before day 7, wound closure in the ChitoSilk BioPatch group was difficult to observe and record with coverage of the nanopatterned silk screen. Since the shedding of the silk screen was synchronized with wound contraction between day 7 and day 10 after surgery in the ChitoSilk BioPatch group, the wound closure rates in all groups were calculated on days 10 and 14 after surgery (see Fig.22A ).
[0208] Wounds treated with BMPS-dACM hydrogel and ChitoSilk BioPatch showed significantly better healing outcomes compared to NC, CS, and BMPS groups. In the BMPS-dACM and ChitoSilk BioPatch groups, higher healing rates were observed macroscopically on days 10 and 14; H&E staining (e.g. Fig. 22B ) showed better neocortical regeneration and neoepidermal formation on day 7 after surgery, as well as more complete epithelialization and dermal regeneration on day 14 after surgery. Sirius red staining (as shown in Figure 23) showed that tighter and better oriented collagen fibers and more collagen I formation were also observed in the BMPS-dACM and ChitoSilkBioPatch groups on days 7 and 14 after surgery. These results indicate that the use of dACM brings significant bioactivity to the biopatch and significantly promotes wound healing. Interestingly, from macroscopic observations and histological evaluations, we observed that the ChitoSilkBioPatch group had a better healing effect than the BMPS-dACM group. Accelerated wound closure ratios and enhanced epidermal and dermal regeneration were observed in the ChitoSilkBioPatch group. In wound healing, the nanopatterned silk screen itself theoretically has limited bioactivity, so the enhancement of wound healing may come from its physical protection of the wound.
[0209] In addition, wounds treated with BMPS hydrogels showed significantly higher macroscopic healing rates and enhanced epithelialization and dermal regeneration quality compared with NC and CS groups. The results indicate that BMPS exhibits stronger bioactivity than CS hydrogels in promoting chronic wound healing.
[0210] In order to further study the potential cellular mechanism of ChitoSilk BioPatch in promoting chronic wound healing, IF staining was used to further evaluate its in vivo immunomodulatory and angiogenic effects (see Figures 24 and 25). The results in Figure 24 show that compared with the NC, CS and BMPS groups, significantly fewer inflammatory macrophages expressing iNOS (M1 phenotype) and more CD206+ inflammatory macrophages (M2 phenotype) were found in the BMPS-dACM and ChitoSilk BioPatch groups on the 7th day after surgery, proving that the incorporation of dACM brought the desired immunomodulatory effect to ChitoSilk BioPatch. In addition, BMPS hydrogels showed significantly stronger immunomodulatory effects than CS hydrogels. Compared with the NC and CS groups, significantly fewer M1 macrophages were observed in wounds treated with BMPS hydrogels. IF staining of CD31 and α-SMA (as shown in Figure 25) showed that the number of new capillaries in the regenerated tissues of the BMPS-dACM and ChitoSilk BioPatch groups was significantly greater than that of the NC, CS and BMPS groups.
[0211] The above results indicate that ChitoSilk BioPatch has ideal biocompatibility and bioactivity. No obvious adverse events or reactions were observed in either group. The excellent bioactivity of ChitoSilk BioPatch comes mainly from dACM and partly from BMPS. As a highly biocompatible natural scaffold and a source of several effective GFs, cytokines and matrix proteins, ACM derivatives have been studied and applied for decades and reported to present various therapeutic advantages in wound healing. AM provides various biological effects, including promoting epithelialization, regulating angiogenesis, inhibiting inflammation and fibrosis, and antimicrobial properties. Here, supplementation of dACM into the biopatch significantly increased the bioactivity and significantly promoted wound healing. Accelerated epidermal and dermal regeneration as well as enhanced angiogenesis and immunomodulatory effects were observed in the BMPS-dACM and ChitoSilk BioPatch groups. Considering the removal of cellular components, in our study, the bioactivity of dACM is probably attributed to the presence of GFs, cytokines and other bioactive proteins. In diabetic wounds, changes in the distribution and function of the cells involved contribute to chronic healing. Intense and persistent inflammation is a major factor affecting the healing process of diabetic wounds (see GFPierce, "Inflammation in non-healing diabetic wounds: the spatiotemporal continuum is crucial," Am. J. Pathol., Vol. 159, No. 2, pp. 399-403, 2001, doi: 10.1016 / S0002-9440(10)61709-9.). Excessive accumulation of proinflammatory macrophages and abnormal polarization of macrophages play a key role in diabetic wound healing.
[0212] Compared with CS, BMPS showed a promoting effect in wound healing and immunomodulation, making it more promising as a scaffold for chronic wound repair. Chitosan and its derivatives have many biological activities, including antimicrobial and anti-inflammatory activities, which have been studied for decades (see P. Feng et al., "Chitosan-based functional materials for skin wound repair: mechanisms and applications," Front. Bioeng. Biotechnol., Vol. 9, February 2021, doi: 10.3389 / fbioe.2021.650598.). However, these activities are considered to be relatively mild activities that require chitosan modification. In this study, a stronger anti-inflammatory activity compared to CS was demonstrated, which may be attributed to the grafted maleimide component, as maleimide and its derivatives have been reported to exhibit anti-inflammatory effects (see Y. Zhang et al., “Design, Synthesis, and Bioevaluation of Novel Caffeinone-Maleimide Hybrids as Effective Anti-inflammatory Agents against LPS-Induced Acute Lung Injury,” Bioorg. Chemistry, Vol. 128, No. 3, p. 106049, 2022, DOI: 10.1016 / j.bioorg.2022.106049. and S.D. Firke and S.B. Baribi, “Synthesis, Bioevaluation, and Molecular Docking Studies of Maleimide Derivatives Featuring a Benzenesulfonamide Group as Selective COX-2 Inhibitors and Anti-inflammatory Agents,” Bioorganic Chemistry, Vol. 128, No. 3, p. 106049, 2022, DOI: 10.1016 / j.bioorg.2022.106049. Med. Chem., Vol. 23, No. 17, pp. 5273-5281, 2015, DOI: 10.1016 / j.bmc.2015.07.070.). In addition, the antimicrobial properties of BMPS demonstrated in our in vitro studies may also contribute to the reduction of inflammatory responses in wounds.
[0213] In the summary of animal study findings, BMPS exhibited stronger anti-inflammatory and regenerative bioactivities than CS, making it more ideal in chronic wound repair. The addition of dACM brought significant bioactivities, including accelerated epidermal and dermal regeneration and enhanced angiogenesis and immunomodulation, and significantly promoted wound healing. The application of nanopatterned silk mesh on the wound did not hinder wound healing. In addition, enhanced wound healing was observed in the ChitoSilk BioPatch group compared with BMPS-dACM, which may come from the physical protection of the wound by the nanopatterned silk mesh. Our proposed biopatch exhibited desirable bioactivities, including antimicrobial, anti-inflammatory, and pro-angiogenic effects, and has great therapeutic potential in chronic wound healing.
[0214] Example II - Preparation of Fetal Bone dECM-Based Antimicrobial Polymer Membranes with Potential Application as Antimicrobial Osteoconductors for Bone Injury Regeneration
[0215] Experiments were designed to prepare an antimicrobial membrane for bone regeneration purposes. Therefore, this membrane has a high potential for use as an osteoconductor in clinical applications, where the tissue / lesion is susceptible to bacterial infection.
[0216] Embodiments of the present disclosure include decellularization of xenogeneic fetal-derived bone ECM to produce mineralized and demineralized fetal goat bone dECM powders / particles, silk fibroin, and combinations thereof, and preparation of nanopatterned xenogeneic fetal bone dECM-based membranes.
[0217] DNA content analysis
[0218] The residual DNA in the fetal goat bone dECM and demineralized fetal goat bone dECM obtained by the method of Example 2 was quantified and compared with the residual DNA in the non-decellularized tissue as a control. The samples were digested at 56°C using the digestion buffer and proteinase K provided in the DNA extraction kit (DNeasy blood and tissue kit, QIAGEN). Subsequently, the DNA in the digested tissue was purified using the kit according to the manufacturer's protocol and purified by The dsDNA quantification kit measures the purified DNA of each sample ( Fig. 27 2700). The experiment was performed in triplicate. The results confirmed that the DNA content of fetal goat-derived bone dECM and demineralized bone dECM was significantly reduced by 99.46% and 99.84%, respectively, compared with control tissue. Therefore, they can be considered as acellular ECM without cell debris.
[0219] Histological analysis
[0220] In order to confirm the effective cell removal and collagen preservation in the dECM of the fetal goat bone sample, the sample produced by the method of Example 2 was subjected to H&E staining and trichrome staining, and the stained sections were evaluated by optical microscopic observation. In the black and white images of H&E staining, the nucleus appears as a black dot, while the cytoplasm and ECM appear in gray, as shown in FIG. Figures 28A to 28C 2800, 2810, and 2820. In the black and white images of trichrome staining, collagen fibers appear in gray, and cell nuclei appear in black dots ( Figures 29A to 29C ).like Figures 28A to 28C , 29A to 29C 2900 2910 2920 , the two decellularization methods of Example 2 substantially eliminated cells from the tissue structure while ensuring good preservation of collagen.
[0221] Scanning electron microscopy (SEM) evaluation
[0222] The morphology of the dECM-silk basement membrane prepared by the method of Example 2 was studied under SEM. SEM images show that adding silk fibroin to bone demineralization dECM digests results in the formation of microfibers in the matrix structure. In addition, the increase in silk fibroin content results in larger microfibers in unreinforced fetal bone dECM-silk membranes. At the same time, the sample with the highest silk concentration shows equiaxed granular structure cracking, resulting in a more fragile platform. The sample is too brittle to be processed and successfully peeled off from the mold ( Fig.30 3000). The morphology of the nanopatterned unreinforced dECM-silk (1:1) shown in Figure 31A3100 confirms the formation of hexagonal close-packed nanocones on the surface prepared from both demineralized dECM and silk fibroin. In addition, nanocones are also expressed on the surface of microfibers in the membrane, making the microfibers uniformly distributed with hexagonal close-packed arrays of nanocones on the substrate surface.
[0223] Atomic force microscopy (AFM) analysis
[0224] The compressive elastic modulus of the dECM-silk membrane of Example 2 was measured by the Hertz model as described above according to the force-displacement curve obtained by AFM analysis. The AFM study was performed in triplicate. It can be seen that the compressive elastic modulus of the unreinforced fetal bone dECM-silk membrane is enhanced by increasing the volume ratio of the silk fibroin solution relative to the demineralized bone dECM digest. The elastic modulus of the sample with 20% silk was 1.34 ± 0.1 GPa, which increased to 1.46 ± 0.2 GPa once the silk concentration increased to 80%. However, the samples with higher silk content were more brittle, and the best samples in terms of processability and mechanical properties contained 50% silk fibroin with a compressive elastic modulus of 1.35 ± 0.05 GPa. The unreinforced dECM-silk matrix was further enhanced with 1, 2 and 3% w / v bone dECM powder, resulting in its elastic modulus being enhanced to 1.39 ± 0.5, 1.54 ± 0.5 and 1.63 ± 0.09 GPa, respectively.
[0225] Figures 32A to 32D The morphology of 2% dECM-silk hybrid composite and its nanopatterned counterpart are shown in (3200, 3210, 3220, 3230). The yellow arrows indicate the dispersion of fetal bone dECM particles with a size of ≤200 μm in the matrix.
[0226] Bacteria research
[0227] In vitro antibacterial properties
[0228] A strain of Staphylococcus aureus (ATCC29213) was used in these evaluations. The bacteria were cultured in LB medium at 220 rpm, 37°C in a shaking incubator overnight. The bacterial optical density was adjusted to 0.1 (OD600 = 0.1) by supplementing with appropriate fresh medium for reactivation for 3 hours. To evaluate the antibacterial properties of the samples, the membranes were UV sterilized before the experiments. O 2 The sterilized samples were then plasma etched for 5 min to increase the hydrophilicity of their surfaces for subsequent in vitro studies. 2 Plasma-etched unreinforced dECM-silk (1:1), nanopatterned unreinforced dECM-silk (1:1), O 2 Plasma-etched 2% dECM-silk hybrid composites, nano-patterned 2% dECM-silk hybrid composites, and ciprofloxacin at a concentration of 20 mg / mL as a positive control were used to test the antibacterial properties of the materials against microorganisms. In order to select the optimal initial concentration of the bacterial solution for this test, the nano-patterned 2% dECM-silk hybrid composite was treated with 100 μL of bacterial solution of different concentrations for 3 hours. The wells of the 24-well plate were used as controls. The gaps between the wells of the well plate were filled with sterile water to avoid evaporation of the culture medium. At the 3-hour time point, the attached bacteria were separated from the sample by adding 900 μL of culture medium to each well and pipetting up and down. Next, an appropriate dilution of the bacterial suspension was used and spread on a solid agar plate and cultured for another 16 hours to count the nucleated CFU. Fig.33 3300 confirmed that even when the concentration of the bacterial solution was adjusted to 10 9 CFU / mL, the nanopatterned 2% dECM-silk hybrid composite also had significant antibacterial properties. Therefore, in order to compare the antibacterial properties of the samples with each other, a high concentration of Staphylococcus aureus (10 8 CFU / mL) were used for the rest of the experiments. To this end, sterilized samples were added to a 24-well plate and 100 μL of a concentration of 10 8 CFU / mL of diluted bacterial solution was cultured on the surface of each sample for 1, 3, 6 and 24 hours. At the same time, the gaps between the wells were filled with sterile water to avoid evaporation of the culture medium. At the specified time point, the attached bacteria were separated from the sample by adding 900 μL of culture medium to each well and pipetting up and down. Next, appropriate dilutions of the bacterial suspension were used at each time point and spread on solid agar plates and cultured for another 16 hours to count CFU.
[0229] Figure 343400 shows a photograph of an agar plate. 2Plasma-etched unreinforced dECM-silk (1:1), nanopatterned unreinforced dECM-silk (1:1), O 2 The plasma-etched 2% dECM-silk hybrid composite, the nanopatterned 2% dECM-silk hybrid composite and the wells treated with ciprofloxacin at a concentration of (20 mg / mL) as a positive control were then cultured with Staphylococcus aureus bacterial cells for 1, 3, 6 and 24 hours. The surface nanocones of both nanopatterned samples significantly increased the O 2 Plasma-etched non-reinforced dECM-silk (1:1) and O 2 Antibacterial properties of plasma-etched 2% dECM-silk hybrid composites) against Staphylococcus aureus, although all membranes containing fetal bone dECM (mineralized or demineralized) showed interesting antibacterial properties considering the very high initial concentration of the bacterial solution (108 CFU / mL). In addition, 2% dECM-silk hybrid composites with or without nanocones showed better antimicrobial effects against Staphylococcus aureus compared to unreinforced membranes.
[0230] Adhesion test
[0231] Silk films with and without nanopatterns were used for bacterial adhesion testing. Before the experiment, 2 Plasma-etched non-reinforced dECM-silk (1:1), nanopatterned non-reinforced dECM-silk (1:1), O 2 Samples of plasma-etched 2% dECM-silk hybrid composites and nanopatterned 2% dECM-silk hybrid composites were UV sterilized in a biosafety cabinet. Staphylococcus aureus was cultured in LB medium at 220 rpm and 37°C overnight in a shaking incubator. The bacterial optical density was adjusted to 0.1 (OD600 = 0.1) by supplementing with appropriate fresh medium and reactivated for 3 hours. To evaluate bacterial adhesion, the bacterial concentration was adjusted to 10 8 CFU / mL, and 100 μL of the solution was spread on the substrate surface to simulate immersion. At different time points (1, 3, 6 and / or 24 hours), the culture medium was removed and the substrate was fixed with 2.5% glutaraldehyde overnight. Afterwards, the samples were washed with 10%, 30%, 50%, 75% and 96% ethanol in sequence and dried at 25°C before being observed with SEM (shown in Figures 35A to 35D (3500, 3510, 3520, 3530) and 36A to 36D (3600, 3610, 3620, 3630). Figures 35A to 35D It can be clearly seen that once in Figures 35A 3500 to 35B 3510 2Plasma etched unreinforced dECM-silk (1:1) and Fig.35C 3520 to 35D 3530 After culturing for 3 hours in nanopatterned unreinforced dECM-silk (1:1), the bacterial cell wall was destroyed. This is due to the effective antibacterial activity of AMPs present in the fetal demineralized bone decellularized extracellular matrix component of the membrane. AMPs in living organisms are produced by their innate immune system to fight fungi, viruses and bacteria. They are usually shorter than 45 amino acids and are amphipathic and cationic. These peptides vary significantly in structure, function and sequence, even between closely related species. This AMP is able to interact with the negatively charged lipids of the bacterial membrane, which leads to permeabilization and destabilization of the membrane, while causing multiple stresses on the bacterial membrane proteins and leakage of the contents in the bacterial cells, as shown in Figure 35A3500. Several mechanisms have been proposed to describe the mode of action of AMPs. For example, some models have been proposed to explain the interaction of α-helical AMPs with bacterial membranes, such as "ring pores", "barrel walls" and "carpet models". All mechanisms lead to severe damage to the bacterial membrane, resulting in bacterial death. As Figures 35A to 35D As shown in (3500, 3510, 3520, 3530), the holes located in the bacterial cell wall demonstrate severe damage to the membrane that inhibits bacterial growth.
[0232] The peptides can be derived from collagen, non-collagenous proteins and growth factors. Moreover, the degradation products of ECM components bring antimicrobial activity because most of them have hydrophobic and basic amino acid sequences, resulting in antibacterial activity against Gram-positive and Gram-negative bacteria. Some AMPs are cationic, and since bacterial membranes are highly negative due to their surface components, they will interact with each other, and thus electrostatic forces will affect the antibacterial activity of AMPs.
[0233] Although both samples have antibacterial effects against Staphylococcus aureus, compared with their counterparts without nanofeatures ( Fig.35A Compared with Figure 3500 to Figure 35B 3510), the nanopatterned samples had a lower number of bacteria on their surface (Figures 35C 3520, 35D 3530). This may be due to the synergistic antibacterial effect of the nanocones interacting with the cell wall and the dECM AMPs from embryonic demineralized bone used in the nanopatterned non-reinforced dECM-silk (1:1) matrix, resulting in a significant reduction in attached bacteria on the surface.
[0234] In O 2The SEM images of Staphylococcus aureus bacteria after 3 h of incubation on the plasma-etched 2% dECM-silk hybrid composite and nanopatterned 2% dECM-silk hybrid composite surfaces (Figures 36A3600 to 36B3610) confirmed the antibacterial properties of both samples, as the bacterial cell walls cultured on these surfaces were damaged (Figures 36C3620 to Fig.36D 3630). However, the synergistic effect of the nanocones interacting with the cell wall and the dECM antimicrobial peptides used in the nanopatterned 2% dECM-silk hybrid composite matrix for embryonic bone (both mineralized and demineralized) resulted in a significant reduction in bacteria attached to the surface and more significant bacterial membrane damage. 2 Some holes were generated on the bacterial cell walls in the plasma-etched 2% dECM-silk hybrid composites, but more severe damage could be detected on the cell walls of bacteria cultured on the nanopatterned surfaces, and more bacterial fragments could be clearly seen in the SEM images of the nanopatterned 2% dECM-silk hybrid composites ( Fig.36C 3620 to 36D 3630).
[0235] Compare Fig.35D 3530 and Fig.36D 3630, due to the presence of more AMPs on their surface due to the incorporation of bone dECM particles (in addition to the demineralized bone dECM digest in the matrix) in the nanopatterned 2% dECM-silk hybrid composites and the resulting stiffer nanocones had a synergistic antibacterial effect, thus leading to more severe bacterial cell wall damage compared with nanopatterned unreinforced dECM-silk (1:1).
[0236] Figures 37A to 37D (3700, 3710, 3720, 3730) shows that 2 Scanning electron microscopy (SEM) images of Staphylococcus aureus cultured on plasma-etched non-reinforced dECM-silk (1:1) and nanopatterned non-reinforced dECM-silk (1:1) for 24 hours confirmed damage to the bacterial cell wall over a 24-hour period on both samples. However, the synergistic effect of the nanocones and dECM antimicrobial peptides from fetal demineralized bone used in the nanopatterned non-reinforced dECM-silk (1:1) matrix resulted in reduced bacterial attachment on the surface or exhibited enhanced antimicrobial activity compared to their counterparts without nanopatterns. Figures 38A to 38D (3800, 3810, 3820, 3830) shows that 2Scanning electron microscopy (SEM) images of Staphylococcus aureus cultured for 24 hours on plasma-etched 2% dECM-silk hybrid composites and nanopatterned 2% dECM-silk hybrid composites confirmed the antibacterial properties of both matrices as the bacterial cell wall was significantly damaged. However, the synergistic effect of the rigid nanocones and fetal (mineralized and demineralized) dECM AMPs used in the matrix of the nanopatterned 2% dECM-silk hybrid composites resulted in a significant reduction in bacteria attached to the surface and caused more severe bacterial membrane damage. There were almost no live bacteria on the surface and only bacterial fragments were seen on this substrate. Comparison Fig.37D 3730 and Fig.38D 3830, due to the presence of more AMPs on the surface of the nanopatterned 2% dECM-silk hybrid composite due to the incorporation of bone dECM particles (in addition to the demineralized bone dECM digest in the matrix), and the resulting stiffer nanocones had a synergistic antibacterial effect, resulting in more severe bacterial cell wall damage compared to the nanopatterned unreinforced dECM-silk (1:1). Although bacterial cell walls were damaged on both surfaces, the damage caused by the nanopatterned 2% dECM-silk hybrid composite was more significant, as only cell fragments were detected on this surface, while round bacteria with obvious holes in the membrane were seen on the surface of the corresponding material without bone dECM particles.
[0237] It will be appreciated by those skilled in the art that various changes and / or modifications may be made to the present disclosure as shown in the specific embodiments without departing from the spirit or scope of the present disclosure as broadly described. Therefore, the present embodiments are to be considered in all aspects as illustrative and not restrictive.
[0238] Unless otherwise indicated, any reference to prior art contained herein should not be taken as an admission that the information is common general knowledge.
Claims
1. A composition for tissue regeneration in a subject, characterized in that: The invention relates to a composition comprising: a xenogeneic decellularized extracellular matrix (dECM) component containing a biomaterial and a polymer component; wherein the composition is prepared by a method comprising: (i) isolating tissue from a donor animal to obtain the biological material; (ii) decellularizing the biomaterial to obtain the decellularized extracellular matrix component; and (iii) combining the decellularized extracellular matrix component with the polymer component to prepare the composition with enhanced antimicrobial properties.
2. The composition according to claim 1, characterized in that in, The tissue is selected from one or more of the fetal membrane, or fetal or neonatal bone of the donor animal.
3. The composition according to claim 1, characterized in that in, The donor animal is a goat fetus or a goat neonate.
4. The composition according to claim 1, characterized in that in, The donor animal is a goat fetus or goat neonate having a gestational age of about 12 weeks to about 18 weeks.
5. The composition according to claim 1, characterized in that in, The tissue is selected from one or more of fetal membrane tissue and / or fetal or neonatal bone tissue from the donor animal.
6. The composition according to claim 5, characterized in that in, The tissue is fetal membrane tissue including one or more of amnion and / or chorion.
7. The composition according to claim 1, characterized in that in, The tissue is fetal or neonatal bone tissue including one or more of cortical bone and / or cancellous bone.
8. The composition according to claim 1, characterized in that in, The decellularized extracellular matrix component is in the form of a powder, a solution, a hydrogel, a scaffold, a membrane, a film, a coating or a combination thereof.
9. The composition according to claim 1, characterized in that in, The surface morphology of the decellularized extracellular matrix component is porous, smooth, nano-patterned, or a combination thereof.
10. The composition according to claim 1, characterized in that in, The polymer component is derived from one or more natural polymers.
11. The composition according to claim 1, characterized in that in, The polymer component is silk fibroin, chitosan or a combination thereof.
12. The composition according to claim 1, characterized in that in, The polymer component is silk fibroin in the form of a stretchable film or a rigid film.
13. The composition according to claim 1, characterized in that in, The polymer component is pure chitosan or functionalized chitosan.
14. The composition according to claim 1, characterized in that in, The polymer component is functionalized chitosan produced by mixing chitosan with N-(β-maleimidopropoxy)succinimide ester at room temperature for about 6 hours.
15. The composition according to claim 1, characterized in that in, The polymer component is a membrane, a scaffold, a hydrogel, or a combination thereof.
16. The composition according to claim 1, characterized in that in, The surface morphology of the polymer component is porous, smooth, nano-patterned, or a combination thereof.
17. The composition according to claim 1, characterized in that in, The nano-patterned surface morphology of the decellularized extracellular matrix component and / or the polymer component provides enhanced antimicrobial properties to the composition.
18. The composition according to claim 1, characterized in that in, The composition is a stent, a membrane or a coating.
19. The composition according to claim 1, characterized in that in, The composition is applied to the skin or bone tissue of a subject in need of tissue repair.
20. A method for preparing a decellularized extracellular membrane (dECM) composition for use in tissue regeneration in a subject, the composition comprising a decellularized extracellular matrix component and a polymer component, characterized in that: The method comprises the following steps: (i) obtaining target tissue from a donor animal; (ii) decellularizing the target tissue and removing genetic material from the target tissue to obtain the decellularized extracellular matrix component; and (iii) combining the decellularized extracellular matrix component with the polymer component to prepare a composition with enhanced antimicrobial properties.
21. The method according to claim 20, characterized in that in, Decellularizing the target tissue includes: treating the target tissue with a chemical reagent; wherein the chemical reagent includes a detergent, an enzyme, a chelating agent, or a combination thereof.
22. The method according to claim 20, characterized in that in, Decellularizing the target tissue comprises the following steps: (i) washing the tissue in a hypotonic buffer optionally supplemented with antibiotics, chelators and a protease inhibitor cocktail; (ii) washing the tissue in an isotonic buffer, wherein the isotonic buffer optionally contains a detergent, a chelating agent, a protease inhibitor cocktail, and an antibiotic; (iii) washing the tissue with an isotonic buffer; (iv) washing the tissue in a hypotonic buffer; and (v) washing the tissue with an isotonic buffer and removing the genetic material from the target tissue to obtain the decellularized extracellular matrix component.
23. The method according to claim 20, characterized in that in, Decellularizing the target tissue includes the optional step of physically disrupting the target tissue by freeze-thaw, grinding, homogenization, osmotic shock, or a combination thereof.
24. The method according to claim 20, characterized in that in, The polymer component is derived from one or more natural polymers.
25. The method according to claim 20, characterized in that in, The polymer component is silk fibroin, chitosan or a combination thereof.
26. The method according to claim 20, characterized in that in, The polymer component is silk fibroin in the form of a stretchable film or a rigid film.
27. The method according to claim 20, characterized in that in, The polymer component is pure chitosan or functionalized chitosan.
28. The method according to claim 20, characterized in that in, The polymer component is functionalized chitosan produced by mixing chitosan with N-(β-maleimidopropoxy)succinimide ester at room temperature for about 6 hours.
29. The method according to claim 20, characterized in that in, The polymer component is a membrane, a scaffold, a hydrogel, or a combination thereof.
30. The method according to claim 20, characterized in that in, The surface morphology of the polymer component is porous, smooth, nano-patterned, or a combination thereof.
31. The method according to claim 20, characterized in that in, The nano-patterned surface morphology of the decellularized extracellular matrix component and / or the polymer component provides enhanced antimicrobial properties to the decellularized extracellular membrane (dECM) composition.
32. The method according to claim 20, characterized in that in, The decellularized extracellular matrix component is in the form of powder, hydrogel, scaffold, membrane, film, coating or a combination thereof.
33. The method according to claim 20, characterized in that in, The surface morphology of the decellularized extracellular matrix component is porous, smooth, nano-patterned, or a combination thereof.
34. The method according to claim 20, characterized in that in, The decellularized extracellular membrane (dECM) composition is a scaffold, a membrane or a coating.
35. The method according to claim 20, characterized in that in, The donor animal is a goat fetus or a goat neonate.
36. The method according to claim 20, characterized in that in, The target tissue is selected from one or more of fetal membranes, or fetal or neonatal bones from the donor animal.
37. The method according to claim 20, characterized in that in, The donor animal is a goat fetus or goat neonate having a gestational age of about 12 weeks to about 18 weeks.
38. The method according to claim 20, characterized in that in, The target tissue is selected from one or more of fetal membrane tissue and / or fetal or neonatal bone tissue from the donor animal.
39. The method according to claim 20, characterized in that in, The target tissue is fetal membrane tissue including one or more of amnion and / or chorion.
40. The method according to claim 20, characterized in that The target tissue is fetal or neonatal bone tissue including one or more of cortical bone and / or cancellous bone.
41. The method according to claim 20, characterized in that in, The decellularized extracellular membrane (dECM) composition is administered to skin or bone tissue of a subject in need of tissue repair.
42. A method for repairing skin or bone tissue of a subject, characterized in that: The method comprises: applying the decellularized extracellular membrane (dECM) composition of claim 20 to the skin or bone tissue of a subject in need of tissue repair.